The gelation mechanism and network structure of polysaccharide food gels as studied from macroscopic, microscopic to molecular levels — A review of methodologies - Weifeng Li; Xi Yang; Haopeng Wang; Yisu Yang; Xingfeng Shao; Marwa E. Atya; Shingo Matsukawa (Food Hydrocolloids, 2027)

Shoot two birds with one stone: chemical and biological mechanisms of calcium-phosphorus modification for enhancing carbon sequestration and heavy metal stabilization of biochar - Xiao Yang; Jianhua Li; Gaoyuan Gu; Yushi Li; Chong Peng; Yuanfei Wang; Yu Zhang; Yun Li; Shuyi Yang; Tao E (Bioresource Technology, 2027)

Complex evolutionary history of Rosales mediated by extensive incomplete lineage sorting and hybridization - Luxian Liu; Weiwei Lv; Douglas E. Soltis; Hans Peter Comes; Yonghua Zhang; Yu Shi; Shufen Li; Meizhen Wang; Wujun Gao; Pan Li (Molecular Phylogenetics and Evolution, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Berberine-associated lipid-inflammatory regulation in atherosclerosis: an integrative transcriptomic, single-cell, and in vivo study - Diwei Yao; Xianqin Wang; Yihang Li; Yiping Wang; Xue Mao; Yu-E Wang; Yu Qi; Yanning Qiu; Jiale Chen; Lian Shu (Functional & Integrative Genomics, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

High current loading drives unprecedented CO2 reduction kinetics in microbial electrosynthesis of methane - Haopeng Wang; Haowen Zhang; He Dong; Haoyong Li; Qianglong Chai; Zhongzheng Li; Yidan Wang; Yan Dang; Dawn E. Holmes (Chemical Engineering Journal, 2026)

Cavity-assisted multi-interface heat management in a hollow aerogel evaporator for efficient and salt-resistant solar evaporation - Long Peng; Haifeng Zhang; Tianxiang Zhou; Mingyu Wang; Zhijian Li; Xiangxin Hou; Danyan Qin; Yi E; Xianbao Wang; Liangyou Lin (Journal of Environmental Chemical Engineering, 2026)

An integrated multiscale air quality modelling framework for industrial park pollution: Linking local emissions to regional transport - Tao Wang; Jie Li; Joshua S. Fu; Wei Wang; Bing Liu; Bin Zhao; Yibo Zhang; Jinxiu Pan; Feng Sun; Xiu’e Shen; Zhe Wang; Xiao Tang; et al. (Journal of Environmental Sciences, 2026)

Maize attainable yields across China reveal unrealized potential for sustainable food security - Jingjing Wang; Zhijuan Liu; Zhenkang Yang; E Li; Jiangjiang Xia; Jingjin Gong; Huihui Qu; Tao Li; Xiaomao Lin; Xiaoguang Yang (Field Crops Research, 2026)

Cyclodextrin-engineered bioinspired nanozyme microneedle for adaptive theranostic regulation of hyperuricemia and gout - Xu-Wei Qi; Hua-Zhou Niu; Ya-Hui Chen; Ye-Tao Zhang; Jing Li; Zu-E Hu; Jia-Xin Wang; Yi-Qi Liu; Bang-Jing Li; Sheng Zhang (Carbohydrate Polymers, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Zn-La staged modification of reed biochar for adsorption of tetracycline hydrochloride and mechanism study - Zhengqi Liang; Xiongyan Gao; Yushan Li; Xu Liu; Boxing An; Yingying Zuo; Ling Wang; Jiahui Fu; Meili E (Journal of Water Process Engineering, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Mechanism of rice protein amyloid fibrils-induced structural changes of soybean protein during high-moisture extrusion: Focusing on multi-scale structural evolution - Jinming Ma; Kaizhi Li; Deyin Pan; Peng Wang; Mohamed E. Hassan; Wenyi Yang; Tianshu Zhang; Xiaoshuai Yu; Baoxin Lu; Zhigang Xiao (Food Research International, 2026)

Polydopamine-directed facet-selective UIO-67 growth to realize aligned pore channels for low-tortuous Li+ transport in composite solid-state electrolytes - Xiaoxiao Li; Xuping Jia; Kai Chen; Zhaoyang Wang; Jiajia Huang; Chao Zhang; Elke Debroye; Xing Yi Ling; Feili Lai; Yue-E Miao (Chemical Engineering Journal, 2026)

Multiphase coupling of phosphorus and organic matter across water–particle interaction in aquaculture ponds - Xiangcheng Kong; Sarah E. Rice; Harlow S. Kramer-Dew; Andrew R. Zimmerman; Christopher J. Martyniuk; Young Gu Her; Eban Bean; Jonathan D. Judy; Yuncong Li; Alan E. Wilson; Dengjun Wang (Journal of Hazardous Materials, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

Production of hydrogen during electro-oxidation of urea using Ni-based catalysts modified with Mn and Zn supported on a Vulcan carbon matrix - F.A. Gómez-Gómez; E. Castañeda-Morales; S. Vázquez-Bautista; Yueyin Li; L. Chen; J.A Wang; E. Ramírez-Meneses; D.M. Morales; A. Susarrey-Arce; A. Manzo-Robledo (Fuel, 2026)

MgI2 immobilized nitrogen and phosphorus co-doped hollow carbon cubes as a multifunctional host for high-performance lithium‑sulfur batteries - Sheng Liang; Cong Li; Zi-Hao Chen; Lei Hu; Xin Liang; Ling-Li Liu; Li-Li Wang; Ning-Ning Zhou; Bin Chen; Wen-Yu Gu; San-E Zhu (Chemical Engineering Journal, 2026)

Bio-inspired aerogel fibers with cross-scale structural customization via cryogenic 3D printing for intelligent perception - Baisong Yang; Yaohui Yang; Daxiang Zhu; Zhuoying Li; Chaoqian Chen; Jie Pan; Lijie Yang; Yijia Wang; Yu Zhang; Jinxin Chen; Jiancheng Cai; Qiping Xu; et al. (Chemical Engineering Journal, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

Chinese AgroMeteorological Model CAMM 2.0–3.0: System Framework, Mechanistic Innovations, and Operational Applications - Yuping Ma; Dingrong Wu; Jianying Yang; Youhao E; Qi Wang; Shuang Sun; Linli Sun; Min Xu; Dianchen Han; Yang Li; Yuanda Zhang; Qianchuan Mi; et al. (Journal of Meteorological Research, 2026)

Metallogenic Mechanism for the Deep Part of the Jiaojia Gold Zone in the Eastern North China Craton (Jiaodong): Constrains from Pyrite Re-Os Geochronology, in-situ Trace Elements and Sulfur Isotope Compositions - Naijie Chi; Zuozhen Han; Xuefeng Yu; Wei Shan; Chuan’e Liu; Xiufeng Wang; Zengsheng Li; Shenghu Li; Chenxi Zhang; Xiangxian Ma (Journal of Earth Science, 2026)

The role of ecosystem conservation and restoration in achieving the SDGs - Yizhong Huan; Guangjin Zhou; Alice C. Hughes; Xiaoyun Li; Peng Hou; Marco Lambertini; Tao Liang; Wenwu Zhao; Binoy Sarkar; Alexandre Betinardi Strapasson; Yiming Su; Xiaoman Liu; et al. (Science Bulletin, 2026)

Neotropical terrestrial records indicate colder, more densely vegetated lowland landscapes between the middle and late Miocene - Elena Stiles; Katharine W. Huntington; Zhennan Wang; Andrew Schauer; Nitzan Yanay; Carmala Garzione; Camilo Montes; Daniel E. Góngora; Andrés Vanegas; César Perdomo; Lin Li; René López-Camacho; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Elucidating the role of ammonia doping in modulating combustion dynamics in ethane fuel-rich jet flames - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Ahmed E. Mansy; Muhammad Yousuf; Kai-Ru Jin; Du Wang; Boyang Su; Aqsa Liaqat; Mohammed Khalil; Zhi-Min Wang; Qingli Li; et al. (Fuel, 2026)

Triplex-helix molecular beacon-enabled CRISPR/Cas12a biosensor for sensitive detection of SARS-CoV-2 - Yuesheng Wang; Shuying Zhang; Jingyu Chen; Ge Qin; Qiongwen Zhang; Yuxi Liu; Dan Yue; Fanting Wang; Shan Wei; Di Wu; Wenqiao Zang; Li-e Liu; et al. (Chemical Engineering Journal, 2026)

Optimization of Agrobacterium-mediated transformation of commercial heirloom tomato cultivars to develop novel traits via CRISPR/Cas9 genome editing - Jordan Oxendine; Elsa Ibarra-Reyes; Junchi Ma; Carrie Li; Sarah Baron; Allison E. Hwang; Ruiting Wang; Daniel Rodriguez-Leal (Planta, 2026)
Main conclusion Trait development for commercial heirloom tomatoes can be advanced by optimization of tissue culture and transformation via Agrobacterium and CRISPR/Cas9 mutagenesis. Abstract Genetic improvement using new genome editing approaches relies on the efficient delivery of the CRISPR/Cas system in the vegetable crop tomato. Previous protocols for tomato transformation have primarily focused on a handful of cultivars (M82, Ailsa Craig, Microtom, Sweet-100) with very little commercial relevance, and it is not clear if these protocols can be implemented directly in other commercially relevant varieties. Heirloom tomatoes are sought for their deep and diverse flavor but have not been subjected to systematic crop improvement via conventional breeding or biotechnology approaches such as transgenesis or genome editing. Therefore, we tested the transformation and regeneration capacity of six different heirloom cultivars known for their superior taste and market relevance in the US. Subsequently, we optimized rooting conditions and used the GRF4-GIF1 chimeric developmental regulator to successfully recover transgenic plants. Finally, we evaluated the efficiency of targeted genetic modification using the CRISPR/Cas9 genome editing system in several of these cultivars. We demonstrate that our optimizations led to successful transformation of several heirloom varieties, including the generation of edited plants for target genes modifying plant architecture and flowering time. Our results set the foundation for a biotechnology platform to deliver improved traits to local and regional heirloom varieties using genome editing.

Transcriptomic and proteomic insights into the molecular mechanism underlying cell wall biosynthesis in Moso bamboo (Phyllostachys edulis) - Xin Geng; Yilan E; Xiaojing Wang; Yanjing Liu; Bowen Li; Qingyu Jin; Yuzhen Chen; Cunfu Lu (Plant Cell Reports, 2026)

Microbial Functional Gene Abundance‐Integrated Modeling of Global Methane Sinks in Upland Soils Under Future Climate Change - Wensheng Xiao; Xiaoqi Zhou; Li Cheng; Paul L. E. Bodelier; Gangsheng Wang; Zhifeng Yang; Jizhong Zhou (Global Change Biology, 2026)
Methanotrophs are key microbial regulators of soil methane (CH 4 ) sinks, but the global impact of their functional gene abundance on CH 4 oxidation remains unquantified. This gap limits the integration of key functional genes abundance parameters (e.g., pmoA ) into soil CH 4 sink model. We integrated meta‐analysis, machine learning, and process‐based modeling to assess the relationship between pmoA gene abundance and soil CH 4 uptake. Our developed Functional Gene Abundance‐Based Methanotrophy Model (FGA‐MeMo) incorporates pmoA as a proxy for CH 4 oxidation capacity, significantly improving model simulations. FGA‐MeMo estimates global upland soil CH 4 uptake at 45.74 ± 0.26 Tg year −1 , which is 56%–58% higher than MeMo model. Under SSP5‐8.5 scenario, this increases to 64.68 ± 0.35 Tg year −1 by 2100, with mid‐ and high‐latitude regions showing enhanced CH 4 oxidation due to greater pmoA abundance. These findings highlight the importance of integrating microbial functional genes into Earth system models for improved CH 4 cycle predictions.

CRISPR-mediated editing of the EMF1 gene improved daily flowering dynamics in Japonica rice - E Li; Nai Wu; Mengchen Li; Yanan Wang; Feiming Wang; Xingxing Luo; Ao Li; Anning Zhang (Plant Physiology Reports, 2026)

Coupling effect of urban building clusters and crosswinds on the aerodynamic performance of high-speed maglev trains - Jianfeng Mao; Xi Wang; Yikang Liu; Zhiwu Yu; Zheng Li; E Deng (Sustainable Cities and Society, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

3D grille evaporator of carbon materials for high-efficiency solar-driven water treatment - Xingyu Shi; Junyang Tao; Yi E; Jie Luo; Wanwei Fu; Zhijian Li; Xianbao Wang (Journal of Environmental Chemical Engineering, 2026)

The Middle-Late Permian alkali granite from the eastern Lhasa Terrane, southern Tibet: Implications for the formation of the Neo-Tethyan Ocean and Cimmerian continental blocks - Haitao Wang; Lingsen Zeng; Li-E Gao; Linghao Zhao; Guangxu Li (Global and Planetary Change, 2026)

W/O/W emulsion-filled egg white gel co-stabilized by protein and γ-cyclodextrin MOFs with multi-chamber encapsulation potential - Chan Li; Xue Yang; Yunfei Zou; Li Zhang; Chuhuan Wei; Yan Ran; E Zhao; Jibiao Yuan; Keshan Wang; Yongguo Jin; Ying Zhou; Qiujin Zhu; et al. (Food Research International, 2026)

Triboelectric-based multiphysical energy-information perception for in-situ wind turbine blade health monitoring - Hengrui Sheng; Rongwei Huang; Jiaxin Hu; Yuejuan Li; Yanshuo Sun; Yusong Cui; Leo N.Y. Cao; Baodong Chen; Herbert E. Huppert; Zhaohui Yao; Zijie Xu; Zhong Lin Wang (Chemical Engineering Journal, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Evaluation of Sugar Beet Breeding Material for Rhizomania Disease Resistance - Shangmin Zhao; Xiaodong Li; E Yuanyuan; Liang Wang; Hui Zhang; Bizhou Zhang; Mengyuan Sun; Bowen Zhang; Huizhong Zhang; Wenzhe Zheng; Zengjuan Fu; Ziqiang Zhang (Sugar Tech, 2026)

The occurrence of extreme heat events offset CO2 fertilization and deteriorate grain quality in double cropping rice systems under projected climate change - Huan Liu; Bin Wang; Yu’e Li; Lu Sun; Longlong Xia; Kees Jan van Groenigen; Yunfan Wan; Tiantian Miao; Weilu Wang; Diego Abalos; Lewis H. Ziska (Agricultural and Forest Meteorology, 2026)

Comparative genotoxicity assessment of ortho-phthalaldehyde using human in vitro organotypic airway epithelial cultures and standard in vitro genotoxicity assays - Yuan Le; Yueyi Sun; Xilin Li; Rebecca Wynne; Nathan Twaddle; Michelle E. Bishop; Frederick A. Beland; William M. Gwinn; Robert H. Heflich; Xuefei Cao; Yiying Wang (Archives of Toxicology, 2026)

Geochemical composition of clinopyroxene phenocrysts in ocean island basalts: implications for magmatic processes beneath Pohnpei Island - Tong Zong; Ligen Han; Zhenggang Li; Chun’e Wang; Yupeng Cao (Journal of Oceanology and Limnology, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

Three-dimensional dust distribution and transport over the northern hemisphere dust belt: Insights from lidar observations - Ruiqi Tan; Tianhe Wang; Ying Han; Jingtao Li; Jingyi Tang; Sichen Wang; Ali Mamtimin; Fan Yang; Chenglong Zhou; Bakhriddin E. Nishonov; Mansur O. Amonov; Sabur F. Abdullaev (Atmospheric Research, 2026)

JsMYB170 modulates flavonols biosynthesis through facilitation of JsFLS1/5 expression in pellicle of Juglans sigillata Dode - Tiantian Fei; Chunxiang Li; Na Wang; Wen’e Zhang; Xuejun Pan (Plant Science, 2026)

Influence of urban turfgrass species on soil organic carbon pool distribution and stability - Yuxin YAN; Fucui LI; Yan ZHANG; Chunbao ZHAO; Yanan ZHANG; Bin TANG; Liebao HAN; Xiang WANG; Hans LAMBERS; Jørgen E. OLESEN (Pedosphere, 2026)

Magma flare-up and Nd isotopic excursion records from the Himalaya: Implications for an early Paleozoic Cordilleran-type orogen - Lilong Yan; Lingsen Zeng; Li-E Gao; Linghao Zhao; Haitao Wang (Lithos, 2026)

Mesoporous CeO2 hollow-nanosphere-supported Ni catalysts for enhanced low-temperature CO2 methanation - Yutong Shen; Yike Gao; Hui Yang; Zhenyu Lu; Mengmeng Li; Cai-e Wu; Shuai Wang; Leilei Xu; Fei Gao; Mindong Chen (Journal of Environmental Chemical Engineering, 2026)

New Potato-Life Cycle Loci Identified by Using an StCDF1-Fixed Population - Ernst-Jan Eggers; Li Shi; Xulan Wang; Marian Oortwijn; Sybille Ursula Mittmann; Richard G. F. Visser; Michiel E. de Vries; Pim Lindhout; Christian W. B. Bachem; Sara Bergonzi (Potato Research, 2026)
Photoperiodic insensitivity has been the selected trait that allowed cultivation of potato outside its centre of origin, to the northern latitudes of Europe and North America. More than a decade ago, Solanum tuberosum CYCLING DOF FACTOR 1 ( StCDF1 ) was identified as the maturity locus, regulating both above and below-ground maturity traits, also referred to as life cycle length and tuberization onset. Following its identification, several genomic studies contributed to the inventorization of the StCDF1 alleles carried by potato cultivars and their wild relatives. At the same time, the role of StCDF1 beyond plant development has started to be elucidated. While the importance of this locus has been widely shown, the presence of this strong QTL hotspot has hampered the identification of additional QTL and genes. Here, we report the use of a StCDF1 -fixed biparental population to map minor QTL for developmental and generative traits. Remarkably, we identified another region on Chr5 controlling several of the analyzed traits, i.e., tuberization onset, anthesis and senescence traits, and harbouring promising candidate genes for further characterization. Furthermore, the study dissected the contribution of self-compatibility to berry and seed set in a field setting prone to open pollination. The use of an StCDF1 -fixed population resulted in a straightforward and cost-effective approach to identify additionally agronomically relevant loci that could be used in future potato breeding.

Prioritizing climate action maximizes synergies among global environmental SDGs: A causal network analysis - Yizhong Huan; Fei Wu; Xiaoyun Li; Jing Wang; Yiming Su; Yang Lan; Feng Kong; Jixi Gao; Wenwu Zhao; Lingqing Wang; Jian Hu; Wenjie Zhao; et al. (Applied Geography, 2026)

Joint Influence of Seed Dormancy and Dispersal Syndrome on Dispersal Distance and Range Size Across Two Climate Regions - Wang Cai; Yuan Liu; YunAo Li; Min Cao; Carol C. Baskin; Jerry M. Baskin; Adriana Alzate; Renske E. Onstein; Jie Yang (Global Ecology and Biogeography, 2026)
Aim Long distance dispersal and the ability to delay germination under unfavourable conditions (dormancy) are critical for plant persistence and range expansion. However, how dispersal syndrome and dormancy interactively shape maximum dispersal distance and species range size across climate regions remains unclear. We tested the hypothesis that a trade‐off between dormancy and dispersal distance operates differently in animal‐mediated versus abiotic dispersal systems, and that climate modulates their influence on range size. Location Global. Time Period Current. Major Taxa Studied Seed plants. Methods We compiled data on dormancy, dispersal syndrome, maximum seed dispersal distance and range size for 631 plant species across 118 families worldwide. We used linear mixed effects models to examine how dormancy and dispersal syndromes interactively shape seed dispersal distance and range size across tropical and temperate regions. Results Non‐dormant species had larger maximum dispersal distances than dormant species, but only in abiotic dispersal systems, consistent with a trade‐off between dispersal and persistence traits (dormancy). In contrast, animal‐mediated dispersal led to larger dispersal distances than abiotic dispersal, regardless of whether species were dormant or not. The influence of dormancy and dispersal syndrome on range size was climate‐dependent. In tropical regions, animal‐mediated dispersal enhanced range size, while dormancy had little effect. In temperate regions, maximum seed dispersal distance was positively associated with range size, but neither dormancy nor animal‐mediated dispersal significantly affected range size. Main Conclusions The interplay between seed dormancy and dispersal syndromes shapes seed dispersal distance and species range size in climate‐specific ways. Animal‐mediated dispersal promotes larger maximum dispersal distances and larger range sizes in tropical regions. In contrast, in abiotic dispersal systems, dormancy leads to relatively small dispersal distances, but dormancy itself does not affect range sizes in temperate or tropical regions. Understanding dispersal‐dormancy dynamics is essential for predicting how plants will respond to environmental changes.

Priorities for enhancing resilience of SDG causal network from a human-nature perspective - Yiming Su; Guangjin Zhou; Mingyuan Wang; Xiaoyun Li; Tao Liang; Lingqing Wang; Jian Hu; Jixi Gao; Wenwu Zhao; Siyuan Tao; Peter E. Holm; Jörg Rinklebe; et al. (Resources, Conservation and Recycling, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

A new method for planning long-distance trails using wilderness quality mapping and trajectory data: A case study of the Taihang Mountain National Forest Trail in China - Yunmiao Chen; Yue Cao; Zhangqian Ye; Tao Liu; Pei Wang; Yunshuang Feng; Lingyun Liao; Mingyang Lv; Zhicong Zhao; Alan E. Watson; Steve Carver; Changjia Li; et al. (Journal of Environmental Management, 2026)

Long-term evidence that controlled-release urea enhances yield and soil fertility while mitigating environmental impacts in double-season rice - Yifan Fu; Wei Yang; Meng Zhang; Xiangning Wu; Guodong Yang; Hongshun Xiang; Chanchan Du; Jinjuan Zhu; Chen Yang; Yunfan Wan; Shaobing Peng; Yu’e Li; et al. (Field Crops Research, 2026)

Biological agents and biomaterials for environmental remediation: applications in water, soil, and air - I U. Islam; S. Bano; M. Mehwish; M. Altaf; R. Shoaib; X. Hu; D. Li; Z. Xiaolian; W. Fatima; N. Shah; X. Wang; E. Yabalak (International Journal of Environmental Science and Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Nonnegligible migration of rubber-derived chemicals from road surface to adjacent greenbelt soil - Zhen-Yu Ge; Hai-Yan Zhang; Xue-E Li; Yue-Hong Liu; Li-Ni Wei; Xiang-Ning Liang; Yan-Feng Lv; Tuan-Tuan Wang; Sai Wang; Jian-Liang Zhao (Journal of Hazardous Materials, 2026)

An efficient multi-objective optimization method for inter-basin water diversion based on the rotation vector method for exploring the convex objective space - Zekun Li; Bin Xu; Ping-an Zhong; Jiaying Tan; Ran Mo; Xinrong Wang; Zichen Ren; Guoqing Wang; Jianyun Zhang; Jiangyuan Li; Scott E. Boyce (Environmental Modelling & Software, 2026)

Interpretable multi-task dual-attention model for forecasting heating load and supply water temperature in district heating systems - Yingfeng Lin; Chun-E Huang; Chunwang Li; Hui Wang; Chuanzhao Zhang (Energy and Buildings, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Development of a high-throughput LLE-UPLC-QqQ-MS/MS method and comprehensive profiling of urinary steroid hormones in Chinese elderly adults - Xiao Ma; Huimin Ren; Li Zhao; Xiaojie Guo; Jiran Zhang; Juan Liu; Xiaona Wang; Mengyao Wang; Yifu Lu; Shilu Tong; Hongyang Cui; Hong Chang; et al. (Analytica Chimica Acta, 2026)

The influence of an environmentally relevant polychlorinated biphenyl mixture on the intestinal microbiota in post-weaning mouse dams - Hui Wang; Laura E. Dean; Xueshu Li; Rachel L. Fitzjerrells; Kai Wang; Ashutosh K. Mangalam; Rachel F. Marek; Conner L. Kennedy; Monica M. Ridlon; Audrey Spiegelhoff; Kimberly P. Keil Stietz; Hans-Joachim Lehmler (Environmental Science and Pollution Research, 2026)
Polychlorinated biphenyls (PCBs) are environmental pollutants linked to neurological impairments by mechanisms involving the gut microbiome. This study examines the effects of maternal exposure to a PCB mixture on the gut microbiome of post-weaning mouse dams. Female C57BL/6 J mice were exposed daily to PCBs at different doses (0, 0.1, 1, or 6 mg/kg body weight/day) before mating, and throughout gestation and lactation. Post-weaning intestinal contents from dams were analyzed to assess microbiome abundance and quantify PCBs and their metabolites. PCB exposure affected the composition of microbial taxa, though not significantly. However, topic modeling analysis identified a distinct microbial community that was significantly more prevalent in the control group compared to post-weaning mouse dams exposed to the MARBLES mixture at medium and high doses. Complex PCBs and metabolite mixtures were detected in the intestinal contents. Certain PCBs and their metabolites were associated with changes in bacterial abundance, as determined by network analysis. These findings show that individual PCBs and their metabolites can affect gut microbial communities, potentially contributing to neurological impairments in mice exposed to PCBs during gestation and lactation. Graphical Abstract

A critical review of textile waste recycling: focusing on global policies, recycling approaches, and recovery products application - Jun Sheng; Hong Chen; Xin Yu; Shiyi Zhao; Hussein E. Al-Hazmi; Xianbao Xu; Xianying Li; Xiaoming Zou; Qiaoying Wang; Xiang Li; Gang Xue (Environmental Science and Pollution Research, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Sustainable production of high-purity crystalline FePO4 from sludge for battery electrodes - Xuan Wang; Yijiao Chang; Zhu Liang; Anjie Li; Yiru Wu; Bohua Wen; Bing Li; Feiyun Sun; Xiao-yan Li; Bruce E. Logan; Lin Lin (Water Research, 2026)

Toxicity and bioconversion: Meta-analytical insights into microplastic effects on black soldier fly rearing - Muhammad Salam; Valentina Grossule; Chujun Li; David Renault; Amira E. Mahmoud; Samia Elouali; Fayuan Wang; Sami Ullah; Viviana Bolletta; Yongchang Cao (Science of The Total Environment, 2026)

Satellite observations reveal ecosystem resistance and resilience to short-term water stress driven by dominant vegetation along a rainfall gradient in Australia - Huanhuan Wang; Qiaoyun Xie; Sally E. Thompson; Caitlin E. Moore; David L. Miller; Erik J. Veneklaas; Richard P. Silberstein; Xing Li; Jingfeng Xiao; Belinda E. Medlyn; William K. Smith (Remote Sensing of Environment, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

Regulatory mechanisms underlying stress-induced accumulation of plant secondary metabolites - Sujing He; Jiangna Wang; Ning Yang; Hongwei Li; Kunqian Li; Lin Li; Wei’e Wen; Tingting Luo; Juanjuan Zhao; Delin Xu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Flavor modulation of braised He Bao carp (Cyprinus carpio) by natural plant spices: Insights from GC–MS, GC–IMS, E-nose, E-tongue, and molecular docking analyses - Yuwei Liu; Yuting Wang; Ziyi Liu; Chang Li; Qiang Yu; Jianhua Xie; You Long; Qianzhu E; Yi Chen (Food Bioscience, 2026)

Self-supplying glucose/oxygen hydrogel enhances dental pulp stem cell survival and vascularized tissue regeneration through Erk1/2-VEGF signaling - Xinyu Liu; Xiaofan Liu; Yuping Zhao; Yang Liu; Huimin Wang; Yi Li; Nan Ma; Hongchen Sun; Fermín E. González; Youliang Zhu; Junfeng Zhou; Yuewei Zhang; et al. (Chemical Engineering Journal, 2026)

Genetic and transcriptomic analysis of microbial electro-extraction for releasing metals from spent Lithium-Ion batteries - Min Li; Danni Zhang; Dawn E. Holmes; Qiuli Xia; Hong Wang; Yongqiang Fan; Hao Song; Dake Xu; Derek R. Lovley (Bioresource Technology, 2026)

Targeting HMGB1 in Microglia Alleviates Neuroinflammation and Modulates the Pro-/Anti-inflammatory Balance of Microglia/Macrophages in Experimental Autoimmune Encephalomyelitis - Yuzhen Li; Ke Lei; Haoyu Wang; Siyu Yang; E Du; Jiapei Dai; Fang Zheng; Jiawen Lei; Huoying Chen; Yan Sun (Molecular Neurobiology, 2026)

Genomic characterization and stress-responsive divergence of HDZip gene family in grapevine (Vitis vinifera L.) - Xue Li; Wen’e Zhang; Yuan Ma; Xuemiao Wang; Jialin Yang; Dongdong Yu; Ruipu Wang; Xuejun Pan (Genetic Resources and Crop Evolution, 2026)

Structural and geochronological studies of the Cona detachment and Cona Rift: Implications for the Miocene evolution of the Cona region - Zhuo Tang; Hanwen Dong; Rongze Fei; Linghao Zhao; Li'e Gao; Yaying Wang; Lilong Yan; Lingsen Zeng (Journal of Structural Geology, 2025)

Corrigendum to “An upscaling approach for estimating field-level irrigation water use through the Budyko framework” [J. Hydrol. 661 (2025) 133785] - Jingwen Zhang; Kaiyu Guan; Murugesu Sivapalan; Chongya Jiang; Ming Pan; Bin Peng; Wang Zhou; Trenton E. Franz; Xiaohong Chen; Kairong Lin; Zejun Li (Journal of Hydrology, 2025)

Dynamic changes in physicochemical properties, flavor, and microbial communities during kombucha fermentation with dominant autochthonous strains inoculation - E. Liao; Na Liu; Qian Li; Han Li; Lu Wang; Wenmin Wu (Food Research International, 2025)

Unveiling the mastery of bacterial navigation: The role of methyl-accepting chemotactic proteins in sensing and mobility through environments and their promising applications in food sustainability - Jiaxun Li; Salma A. Bekhit; Guicheng Zhou; Yangfu Li; Xinmin Liang; Keyuan Qin; Moutong Chen; Liang Xue; Alaa E.-D.A. Bekhit; Juan Wang; Qingping Wu; Yu Ding (Food Research International, 2025)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

A systematic review of protein post-translational modifications in sepsis - Lishun Yang; Zhuang’e Shi; Fuping Wang; Guoyun Shi; Couwen Li; Guobing Chen (Molecular Biology Reports, 2025)

Efficacy and safety of natural killer cell therapy for the treatment of advanced non-small cell lung cancer: A meta-analysis and systematic review - Zhengnan Li; Xiu’e Wang; Shaoqing Chen; Ping Zhang; Xiujuan Wang; Xinye Ni; Chunlin Mou (Immunologic Research, 2025)
To evaluate the efficacy and safety of natural killer (NK) cell therapy for the treatment of advanced non-small cell lung cancer (NSCLC). Relevant studies on NK cell therapy for advanced NSCLC were collected from PubMed, Scopus, Embase and the Cochrane Library up to August, 2024. Two reviewers independently screened the articles and retrieved the data using the Cochrane risk assessment tool. Meta-analysis was conducted with R (version 4.3.1). A total of nine trials were analyzed, including five phase 2 randomized controlled and four phase 1 studies. All were medium to high quality but exhibited high performance and attrition biases. NK cell treatment doses ranged from 1×10 9 to 4×10 9 cells for 2 or 3 cycles. In total, 324 patients with advanced NSCLC were included, comprising 199 who received NK cell therapy and 125 controls, all previously treated with platinum-based regimens. Meta-analysis demonstrated comparable disease control (OR = 2.68; 95% CI: 1.53–4.71) and 1-year survival (OR = 2.54; 95% CI: 1.28–5.02) between groups, with similar adverse events rates (OR = 1.37; 95% CI: 0.35–5.26). Subgroup analyses revealed no significant differences in efficacy. There was considerable heterogeneity among studies ( I ² = 0%–92.5%). Over 39 trials were registered, with only 12 marked as completed and none of the others released the outcome data. Current evidence suggests that NK cell therapy, either alone or in combination, may achieve disease control, survival outcomes and safety profiles that were comparable to existing treatments for advanced NSCLC. These findings remain exploratory and should be confirmed in larger, well-designed trials.

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Metabolomics combined with 16S rDNA revealed the effects of low protein diet on rumen microbiome structure, nitrogen utilization rate and differential metabolites in feces and urine of dairy cows - Yaqiong Ren; Caijuan Yue; Wenzhuo Wang; Li Cai; Yanming Wang; Xiaojing Liu; Depeng Li; Qiao'’e Zhang (Research in Veterinary Science, 2025)

Be–Nb–Ta mineralization in granites: An example from the Nyalam area in the Himalayan belt, southern Tibet - Li-E Gao; Lingsen Zeng; Linghao Zhao; Lilong Yan; Yinglong Di; Guangxu Li; Yaying Wang; Rui Wang; Li Wang (Lithos, 2025)

An upscaling approach for estimating field-level irrigation water use through the Budyko framework - Jingwen Zhang; Kaiyu Guan; Murugesu Sivapalan; Chongya Jiang; Ming Pan; Bin Peng; Wang Zhou; Trenton E. Franz; Xiaohong Chen; Kairong Lin; Zejun Li (Journal of Hydrology, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Chloride-induced electron enrichment strategy: Stabilization mechanism and efficacy of calcium/magnesium modified biochar against chromium contamination in soil - Yan Zhou; Gaoyuan Gu; Jianing Zhang; Yu Zhang; Chong Peng; Yuanfei Wang; Yun Li; Shuyi Yang; Tao E (Environmental Research, 2025)

Dual-strategy stabilization of zinc anodes through solvation regulation and interfacial engineering in aqueous zinc ion batteries - Weilin Yan; Yifan Wang; Lufan Liu; Feiyu Tao; Yang Huang; Zhaoqian Li; Li'e Mo; Hong Zhang; Linhua Hu (Chemical Engineering Journal, 2025)

Garnet dissolution–reprecipitation processes in leucogranitic magma and their profound geochemical consequences - Rui Wang; Li-E Gao; Lingsen Zeng; Lilong Yan; Linghao Zhao; Guyue Hu; Li Wang; Haitao Wang (Chemical Geology, 2025)

Genetic dissection of low-sulfur tolerance via linkage and genome-wide association analyses in soybean [Glycine max (L.) Merr.] seedlings - Kaixin Zhang; Yanning Chen; Sujing Wang; Yu’e Zhang; Yudan Chen; Kaili Ren; Xiao Li; Guizhen Kan; Deyue Yu; Hui Wang (Theoretical and Applied Genetics, 2025)

Association between microplastic exposure and macrolide resistance in mycoplasma pneumoniae pneumonia among younger children: A cross-sectional study in China - Wendi Ma; Lili Zhong; Jingli Yang; Kent E. Pinkerton; Shuli Zhao; Huimin Li; Yinze Xu; Xiuqin Feng; Xuelin Lv; Qiong Wang; Chuyun Yan; Jingjing Zhang; et al. (Journal of Hazardous Materials, 2025)

NH3, N2O, NO and NO2 losses, emission factors and reduction mechanisms under different N managements from greenhouse vegetable soils - Tiantian Miao; Bin Wang; Yunfan Wan; Yu'e Li; Tianjing Ren; Huan Liu; Jiaqi Zhang; Andong Cai; Waseem Hassan (Journal of Environmental Management, 2025)

Efficient Hg(II) removal using recyclable poly(thioctic acid)/SH-UiO-66 functionalized polyacrylonitrile fiber: Multifunctional binding strategy - Ningge Jian; Gaoran Zhang; Hongli Liu; Di Wu; Jia Wang; Yuxin Wang; Yi Cheng; Qingyuan Liu; Yongjun Wu; Li-e Liu (Chemical Engineering Journal, 2025)

Corrosion-resistant, biodegradable green coatings for automotive conductive primers - Yating Li; Xin Tian; Kexin Zhou; Junbo Wang; Chong Peng; Shuyi Yang; Tao E (Chemical Engineering Journal, 2025)

Genome-wide Identification and Expression Analysis of the Argonaute Gene Family in Sugar Beet (Beta vulgaris L.) - Zengjuan Fu; Liang Wang; Xiaodong Li; Yuanyuan E; Yahui Liang; Bizhou Zhang; Shangmin Zhao; Hui Zhang; Wenzhe Zheng; Chen Bai; Mengyuan Sun; Ziqiang Zhang; et al. (Sugar Tech, 2025)

Petrogenesis and tectonic significance of the late Middle Triassic I-type granite in the eastern section of the North Qilian tectonic belt: Constraints on the initiation of post-collision between North China Block and South China Block - Liang'e Chen; Zuochen Li; Xianzhi Pei; Shaowei Zhao; Meng Wang; Hai Zhou; Lei Pei; Youxin Chen; Shang Ji; Weiyi Hou (Lithos, 2025)

Group activity analysis and pollution remediation techniques: Optimization of gel structural properties for efficient copper adsorption by truncating the electron pooling effect on polymer methylene backbones - Changlong Bi; Suya Li; Gaoyuan Gu; Jie Hao; Yupeng Wang; Chong Peng; Shuyi Yang; Tao E (Journal of Hazardous Materials, 2025)

Edge nucleation and bridging effect synergistically in-situ sealed multiple heavy metals in soils - Gu Gaoyuan; Zhang Jianing; Zhou Yan; Ge Ruijie; Li Wenhui; Peng Chong; Wang Yuanfei; Bi Changlong; Yang Shuyi; E Tao (Journal of Hazardous Materials, 2025)

Protecting DNA and improving freeze-drying survival rate of Lactiplantibacillus plantarum LIP-1 through metabolism of hypoxanthine - Xingkun Guo; Qiaoling Zhang; Rongze Ma; Ruoru Zhuang; Jing Li; Shuyi Jiao; Jingjing E; Junguo Wang; Rula Sa (World Journal of Microbiology and Biotechnology, 2025)

Investigating the impact of air pollutants on vegetation and land surface dynamics - Li Wang; Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Dmitry E. Kucher; Aqil Tariq (Theoretical and Applied Climatology, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

Air quality and mental health amid COVID-19: a prospective population-based analysis of the mediating role of daily routine disruptions - Selina Kit Yi Chan; Crystal Jingru Li; Percy Poo-see Tse; Evon Lam Wong; Anan Wang; Huinan Liu; Stevan E. Hobfoll; Chi Yung Jim; Wai Kai Hou (Air Quality, Atmosphere & Health, 2025)

Enhanced sulfamethoxazole (SMX) degradation by Shewanella oneidensis MR-1 via a microbially driven Fenton reaction - Qing-Jiahui Fan; Wei Li; Gen-Ji Yao; Zu-Hao Wang; Han Fu; Yong-Di Liu; Bruce E. Rittmann (Journal of Water Process Engineering, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Quality changes in the physiology, behaviour, nutrition, and taste of Urechis unicinctus during waterless live transportation - Teng Teng; Yuchun Lu; Zichen Deng; Shuqi Wang; Yuting Yang; Huihong Li; Chun-E Liu (Food Chemistry, 2025)

Function sulfur nanodots for the detection and discrimination of allura red from food pigments - Gege Yue; Yuan Li; Xiaozhen Wang; Yu-e Shi; Meng Jiao; Zhenguang Wang (Food Chemistry, 2025)

Early life phthalate exposure impacts gray matter and white matter volume in infants and young children - Emily J. Werder; Kun Lu; Chih-Wei Liu; Jake E. Thistle; Julia E. Rager; Gang Li; Zhengwang Wu; Tengfei Li; Li Wang; Dale P. Sandler; John H. Gilmore; Joseph Piven; et al. (Environmental Research, 2025)

Aluminum ion-activated low-temp pyrolyzed carbon to decontaminate Cr in water and soil - Jianing Zhang; Gaoyuan Gu; Shuyi Yang; Yan Zhou; Jianhua Li; Chong Peng; Yuanfei Wang; Yun Li; Changlong Bi; Tao E (Science of The Total Environment, 2025)

On the long and winding road: unravelling the late emergence of Neolithic agriculture in the Nile Delta - Xiaoshuang Zhao; David Kaniewski; Yanna Wang; Nick Marriner; Alaa Salem; Said E. Alassal; Yan Liu; Feng Jiang; Jing Chen; Qianli Sun; Maotian Li; Ian Thomas; et al. (Quaternary Science Reviews, 2025)

Clinical biomarkers of perioperative neurocognitive disorder: initiation and recommendation - Jianhui Liu; Cheng Li; Junyan Yao; Lei Zhang; Xuan Zhao; Xin Lv; Zhiqiang Liu; Changhong Miao; Yingwei Wang; Hong Jiang; Weifeng Yu; Tianlong Wang; et al. (Science China Life Sciences, 2025)

Behavioral Responses of Migratory Fish to Environmental Cues: Evidence from the Heishui River - Jiawei Xu; Yilin Jiao; Shan-e-hyder Soomro; Xiaozhang Hu; Dongqing Li; Jianping Wang; Bingjun Liu; Chenyu Lin; Senfan Ke; Yujiao Wu; Xiaotao Shi (Fishes, 2025)
Hydropower infrastructure has profoundly altered riverine connectivity, posing challenges to the migratory behavior of aquatic species. This study examined the post-passage migration efficiency of Schizothorax wangchiachii in a regulated river system, focusing on upstream and downstream reaches of the Songxin Hydropower Station on the Heishui River, a tributary of the Jinsha River. We used radio-frequency identification (RFID) tagging to track individuals after fishway passage and coupled this with environmental monitoring data. A Cox proportional hazards model was applied to identify key abiotic drivers of migration success and to develop a predictive framework. The upstream success rate was notably low (15.6%), with a mean passage time of 438 h, while downstream success reached 81.1%, with an average of 142 h. Fish exhibited distinct diel migration patterns; upstream movements were largely nocturnal, whereas downstream migration mainly occurred during daylight. Water temperature (HR = 0.535, p = 0.028), discharge (HR = 0.801, p = 0.050), water level (HR = 0.922, p = 0.040), and diel timing (HR = 0.445, p = 0.088) emerged as significant factors shaping the upstream movement. Our findings highlight that fishways alone may not ensure functional connectivity restoration. Instead, coordinated habitat interventions in upstream tributaries, alongside improved passage infrastructure, are crucial. A combined telemetry and modeling approach offers valuable insights for river management in fragmented systems.

Seasonal climate change characteristics of the Mu Us Sandy Land based on long time scale - Li’e Liang; Yan Chao; Xiaohan Wang; Jiamin Li; Pengfei Ma (Environmental Monitoring and Assessment, 2025)

Biotic and abiotic drivers of soil carbon, nitrogen and phosphorus and metal dynamic changes during spontaneous restoration of Pb–Zn mining wastelands - Sichen Wang; Ting Li; Xinqi Yuan; Ji Yu; Zhifei Luan; Zhaolai Guo; Yadong Yu; Chang’e Liu; Changqun Duan (Journal of Hazardous Materials, 2025)

Identification of polychlorinated biphenyls (PCBs) and PCB metabolites associated with changes in the gut microbiome of female mice exposed to an environmental PCB mixture - Laura E. Dean; Hui Wang; Xueshu Li; Rachel L. Fitzjerrells; Anthony E. Valenzuela; Kari Neier; Janine M. LaSalle; Ashutosh Mangalam; Pamela J. Lein; Hans-Joachim Lehmler (Journal of Hazardous Materials, 2025)

The dual selective adsorption mechanism on low-concentration Cu(II): Structural confinement and bridging effect - Wenhui Li; Gaoyuan Gu; Changlong Bi; Shuyi Yang; Yuanfei Wang; Chong Peng; Yun Li; Tao E (Journal of Hazardous Materials, 2025)

MnSO4-modified woodchip biochar “dual fixation” mechanism: Functional group-electron synergistic stabilization of heavy metals and carbon structure - Jianhua Li; Gaoyuan Gu; Jianing Zhang; Yuanfei Wang; Chong Peng; Yun Li; Shuyi Yang; Tao E (Journal of Environmental Chemical Engineering, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Farmers’ decisions on crop residues utilization, greenhouse gases reduction and subsidy of crop residue-based bioenergy: An agent-based life cycle model - Jiaqi Zhang; Chengxiang Zhuge; Qitong Huang; Bin Wang; Yu'e Li; Peter Oosterveer (Sustainable Production and Consumption, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The molecular mechanism of electrical stimulation on enhancing the foaming properties of egg white liquid - E. Zhao; Chan Li; Jing Yuan; Keshan Wang; Jingchun Ma; Ying Zhou; Qiujin Zhu; Xiaoli Liu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2025)

Dual-interface induced bandgap regulated water-based flexible interactive generator - Ye Zhou; Pengcheng Wu; Yuchang Zhu; Huoerhute Yelemulati; Shanshan Zhu; Keliang Wu; Guihua Meng; Hao Wang; Fathy Hassan; Mohsen Sherif; Guanglin Li; Zhiyong Liu; et al. (Chemical Engineering Journal, 2025)

Synergistic adhesion enhancement of double-crosslinking chitosan hydrogel via catechol-Fe3+ coordination and Schiff base - Guoyu Zhao; Tingting Gu; Licheng Chen; Lei Wang; Yuri V. Petrov; Vladimir E. Baulin; Aslan Yu Tsivadze; Dechang Jia; Yu Zhou; Baoqiang Li (Carbohydrate Polymers, 2025)

Linking soil extracellular enzymes with soil respiration under altered litter inputs - Hao Chen; Qianhao Xu; Kees Jan van Groenigen; Bruce A. Hungate; Pete Smith; Dejun Li; Daryl L. Moorhead; Brooke B. Osborne; Zilong Ma; Jørgen E. Olesen; Chaoqun Wang; Ji Liu; et al. (Agricultural and Forest Meteorology, 2025)

Global Patterns of Climatic Niche Evolution in Angiosperms - Yunpeng Liu; John J. Wiens; Ao Luo; Xiaoting Xu; Dimitar Dimitrov; Xiangyan Su; Yichao Li; Tong Lyu; Loic Pellissier; Niklaus E. Zimmermann; Douglas E. Soltis; Pamela S. Soltis; et al. (Global Ecology and Biogeography, 2025)
Aim A species' rate of climatic niche evolution may reflect its ability to survive changing climates. Yet large‐scale studies of these rates remain limited. Here, we assessed global patterns in climatic niche rates among angiosperms and explored the potential drivers shaping these patterns. Location Global. Time Period Current. Major Taxa Studied Angiosperms. Methods We estimated broad‐scale climatic niches for 231,567 angiosperm species based on distributional data from over 1100 sources. By integrating a published phylogeny of angiosperms, we estimated rates of climatic niche change for each extant species as the difference between its current and ancestral niche divided by the species' age. Global patterns were analysed by averaging rates for all the species found in each geographic unit. We used multiple statistical models to explore the relative contributions of niche width and climatic seasonality to shaping these geographic patterns of niche evolution. We analysed patterns of niche evolution and their underlying drivers separately for temperature‐related and precipitation‐related niches and for different directions of niche evolution (i.e., increases and decreases in species' temperature and precipitation niche values when compared to their most recent ancestors). Results Rates for temperature variables increased with latitude, whereas rates for precipitation variables decreased with latitude. These opposing patterns in temperature and precipitation rates were related to opposing latitudinal patterns in climatic seasonality and species' niche widths for temperature and precipitation. Rates also differed for different directions of niche evolution, with different patterns associated with changes to warmer vs. cooler climates and wetter vs. drier climates. Main Conclusions Our results revealed large‐scale geographic patterns in rates of climatic niche change for temperature and precipitation for the largest clade of angiosperms and their underlying drivers. These findings may have important implications for species' abilities to respond to recent climate change.

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

17β-estradiol inhibits lipopolysaccharide-induced inflammation and pyroptosis of Leydig cells of the domestic yak (Bos grunniens) via the SIRT1/Nox4/ROS pathway - Junyuan Ma; Yanmei Yang; Lin He; Chongfa Yang; Yahua Yang; Yang Li; Wen He; Xiaoying Niu; Zhou Chen; Songming Hu; Jin'e Wang; Yingpai Zhaxi; et al. (Domestic Animal Endocrinology, 2025)

Genetic advancements and future directions in ruminant livestock breeding: from reference genomes to multiomics innovations - Songsong Xu; Zhanerke Akhatayeva; Jiaxin Liu; Xueyan Feng; Yi Yu; Bouabid Badaoui; Ali Esmailizadeh; Juha Kantanen; Marcel Amills; Johannes A. Lenstra; Anna M. Johansson; David W. Coltman; et al. (Science China Life Sciences, 2025)

Corrigendum to “Mid-Holocene hydroclimatic change and hurricane activity in Central America recorded by an Isla de Mona Stalagmite” [Marine Geology 471 (2024) 107289] - Huiru Tang; Liangcheng Tan; Yongli Gao; Jingjie Zang; Le Ma; Yanzhen Li; R. Lawrence Edwards; Hai Cheng; Ashish Sinha; Xiqian Wang; Xing Cheng; Ángel A. Garcia; et al. (Marine Geology, 2025)

Nanoparticle-mediated light-driven LAMP combined with test strips for sensitive and rapid visual detection of antibiotic resistance genes - Yu-E. Gao; Qing Huang; Yue Huang; Li-Xia Yan; Wen-Long Wang; WenFeng Zhao; Yong-Wei Feng; Xiao-Dong Huang; Yi Zhang (Journal of Hazardous Materials, 2025)

Inhibit first and then promote? The relationship between digital economy and urban low-carbon energy security - Haowei Jin; Ju-e Guo; Yanzhao Li; Shubin Wang; Lei Tang (Journal of Cleaner Production, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

The role of lignin-molybdenum disulfide as a nano-filler in enhancing the performance of crosslinked hydrogel nanofibers membrane for lithium-ion battery separators - Yun Dou; Shen Li; Xinxin Zhu; Xia Meng; Shoujuan Wang; Magdi E. Gibril; Fangong Kong (Chemical Engineering Journal, 2025)

Temperature drives reproductive activity in a rare trioecy population of Corbicula clams - Jie Pi; Yangxin Tang; Neil E. Coughlan; Linwei Liu; Xu Wang; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2025)

Evaluation of enzyme activity predictions for variants of unknown significance in Arylsulfatase A - Shantanu Jain; Marena Trinidad; Thanh Binh Nguyen; Kaiya Jones; Santiago Diaz Neto; Fang Ge; Ailin Glagovsky; Cameron Jones; Giankaleb Moran; Boqi Wang; Kobra Rahimi; Sümeyra Zeynep Çalıcı; et al. (Human Genetics, 2025)

CAGI6 ID panel challenge: assessment of phenotype and variant predictions in 415 children with neurodevelopmental disorders (NDDs) - Maria Cristina Aspromonte; Alessio Del Conte; Shaowen Zhu; Wuwei Tan; Yang Shen; Yexian Zhang; Qi Li; Maggie Haitian Wang; Giulia Babbi; Samuele Bovo; Pier Luigi Martelli; Rita Casadio; et al. (Human Genetics, 2025)
The Genetics of Neurodevelopmental Disorders Lab in Padua provided a new intellectual disability (ID) Panel challenge for computational methods to predict patient phenotypes and their causal variants in the context of the Critical Assessment of the Genome Interpretation, 6th edition (CAGI6). Eight research teams submitted a total of 30 models to predict phenotypes based on the sequences of 74 genes (VCF format) in 415 pediatric patients affected by Neurodevelopmental Disorders (NDDs). NDDs are clinically and genetically heterogeneous conditions, with onset in infant age. Here, we assess the ability and accuracy of computational methods to predict comorbid phenotypes based on clinical features described in each patient and their causal variants. We also evaluated predictions for possible genetic causes in patients without a clear genetic diagnosis. Like the previous ID Panel challenge in CAGI5, seven clinical features (ID, ASD, ataxia, epilepsy, microcephaly, macrocephaly, hypotonia), and variants (Pathogenic/Likely Pathogenic, Variants of Uncertain Significance and Risk Factors) were provided. The phenotypic traits and variant data of 150 patients from the CAGI5 ID Panel Challenge were provided as training set for predictors. The CAGI6 challenge confirms CAGI5 results that predicting phenotypes from gene panel data is highly challenging, with AUC values close to random, and no method able to predict relevant variants with both high accuracy and precision. However, a significant improvement is noted for the best method, with recall increasing from 66% to 82%. Several groups also successfully predicted difficult-to-detect variants, emphasizing the importance of variants initially excluded by the Padua NDD Lab.

Genome-wide identification of the sugar beet (Beta vulgaris L.) DMP gene family and its potential role in abiotic stress - Pingan Han; Yue Chang; Kuangang Tang; Liang Wang; Zhijun Xiu; Jing Yang; Haibo Shi; Yahui Liang; Ruifen Sun; Shaofeng Su; Ziqiang Zhang; Zengjuan Fu; et al. (Genetic Resources and Crop Evolution, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The shifts of precipitation phases and their impacts - Xuemei Li; Tao Che; Yuanlong Tang; Huan’e Duan; Guigang Wang; Xu Zhang; Chuanming Yang; Jun Wu; Yue Zhang; Lanhai Li (Science China Earth Sciences, 2025)

Mitochondrial genomes reveal low genetic diversity in snow leopards - Shiqing Wang; Haimeng Li; Yinping Tian; Yu Lin; Yingna Zhou; Jan E. Janecka; Yuan Fu; Yue Ma; Zhen Wang; Tianming Lan (Conservation Genetics, 2025)

Bifunctional probe propelling multipath strand displacement amplification tandem CRISPR/Cas12a for ultrasensitive and robust assay of DNA methyltransferase activity - Fei Yu; Qiongwen Zhang; Tiantian Ma; Shuying Zhang; Fanting Wang; Dan Yue; Shihan Liu; Yueqi Liao; Li-e Liu; Yongjun Wu; Wenqiao Zang (Analytica Chimica Acta, 2025)

Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Field and numerical investigation of groundwater flow and dissolved inorganic nitrogen (DIN) dynamics in a sandy nearshore aquifer - Zhenyan Wang; Clare E. Robinson; Xiaolong Geng; Kai Xiao; Yan Zhang; Xuejing Wang; Wenli Hu; Manhua Luo; Hailong Li (Journal of Hydrology, 2025)

Effects of rumen metabolite butyric acid on bovine skeletal muscle satellite cells proliferation, apoptosis and transcriptional states during myogenic differentiation - Xiao-Wei Wang; Yan-Ling Ding; Cheng-Long Li; Qing Ma; Yuan-Gang Shi; George E Liu; Cong-Jun Li; Xiao-Long Kang (Domestic Animal Endocrinology, 2025)

pH-Responsive lignin-modified copper-based metal-organic frameworks for precision thiamethoxam delivery in the targeted control of red imported fire ants (Solenopsis invicta) - Pengpeng Liu; Amir E. Kaziem; Chen Li; Xin Wang; Shiqi Zhu; Jinzhe Chang; Dongmei Cheng; HanHong Xu; Zhixiang Zhang; Liupeng Yang (Chemical Engineering Journal, 2025)

Self-encapsulation ultra-soft micro-channel with high thermal conductivity and passive radiation cooling - Weiyin Su; Zhonghui Guo; Zeyu Chang; Yuyu E; Wen Li; Jie Li; Shengguang Yuan; Xi Yao; Shengkun Yan; Mingguo Ma; Kun Wang; Jianxin Jiang (Chemical Engineering Journal, 2025)

Chitosan-based composite featuring dual cross-linking networks for the removal of aqueous Cr(VI) - Xueyan Li; Suya Li; Chong Peng; Yuanfei Wang; Yun Li; Shuyi Yang; E. Tao (Carbohydrate Polymers, 2025)

Enhancing direct air carbon capture into microalgae: A membrane sparger design with carbonic anhydrase integration - Rui-Long Wang; Ming-Jia Li; Gregory J.O. Martin; Sandra E. Kentish (Algal Research, 2025)

Characteristics of maternal antibodies transferred to foals raised through maternal equine rotavirus A vaccination - Lianne G. Eertink; Megan Swope; Tirth Uprety; Chithra Sreenivasan; Allen E. Page; Emma N. Adam; Dan Wang; Feng Li (Veterinary Microbiology, 2024)

Tyrobp deficiency blocks NLRP3-mediated inflammation and pyroptosis to alleviate myocardial ischemia-reperfusion injury through regulating Syk - Jie Yu; Xiu’e Mu; Chang Guan; Yaqin Wang; Hongying Li (Tissue and Cell, 2024)

Effects of 28-day nose-only inhalation of PCB52 (2,2′,5,5′-Tetrachlorobiphenyl) on the brain transcriptome - Amanda J. Bullert; Hui Wang; Morgan J. Linahon; Michael S. Chimenti; Andrea Adamcakova-Dodd; Xueshu Li; Michael E. Dailey; Aloysius J. Klingelhutz; James A. Ankrum; Hanna E. Stevens; Peter S. Thorne; Hans-Joachim Lehmler (Toxicology, 2024)

Clay minerals accelerate the formation of indoor biocrusts: Effects and mechanism - Long Qian; Jiping Wang; Jingshang Xiao; Lie Yang; Ling Xia; Shaoxian Song; María E. Farías; Zhaojun Wang; Li Wu (Soil and Tillage Research, 2024)

The potential mediating role of the gut microbiome and metabolites in the association between PFAS and kidney function in young adults: A proof-of-concept study - Hailey E. Hampson; Shiwen Li; Douglas I. Walker; Hongxu Wang; Qiran Jia; Sarah Rock; Elizabeth Costello; Petter Bjornstad; Laura Pyle; Jonathan Nelson; Frank D. Gilliland; Zhanghua Chen; et al. (Science of The Total Environment, 2024)

Cascaded reservoirs promote phosphorus bioavailability of surface sediments in the Upper Mekong River - Zhengjian Yang; QiFeng Min; Xiaojuan Guo; Congfeng Wang; Bi'’e Yan; Xiaoling Li; Defu Liu; Jun Ma; Andreas Lorke (Science of The Total Environment, 2024)

Adsorption and recovery of berberine hydrochloride from wastewater by a novel magnesium-modified biochar: Toward resource utilization of waste dander - Yunyu Zhao; Shuyi Yang; Kexin Zhou; Junbo Wang; Cheng Ji; Yuanfei Wang; Liang Chen; Yun Li; Chong Peng; Tao E (Journal of Water Process Engineering, 2024)

How has the latest IMERG V07 improved the precipitation estimates and hydrologic utility over CONUS against IMERG V06? - Siyu Zhu; Zhi Li; Mengye Chen; Yixin Wen; Shang Gao; Jiaqi Zhang; Jiao Wang; Yi Nan; Sebastian C. Ferraro; Theresa E. Tsoodle; Yang Hong (Journal of Hydrology, 2024)

Durable underwater superoleophobic hydrogels for oil- and Cu(II)-containing water purification - Chang-Lian Xu; Na Ji; Xingyue Wu; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Ting Li; Pietro Paolo de Oliveira e Silva; Guochun Lv; Junzhuo Cai; et al. (Journal of Environmental Chemical Engineering, 2024)

Improvement of soil nutrient cycling by dominant plants in natural restoration of heavy metal polluted areas - Ting Li; Sichen Wang; Luoqi Zhao; Xinqi Yuan; Yuhan Gao; Denggao Fu; Chang'e Liu; Changqun Duan (Environmental Research, 2024)

Degradation of 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV328) in soil by FeS activated persulfate: Kinetics, mechanism, and theoretical calculations - Xiaoyu Li; Yue Bu; Jianqiao Xu; Haifa E. Alfassam; Hassan A. Rudayni; Ahmed A. Allam; Xiaoxue Pan; Zunyao Wang; Ruijuan Qu (Environmental Pollution, 2024)

Biological invasion is eroding the unique assembly of island herpetofauna worldwide - Weishan Tu; Yuanbao Du; Yoel E. Stuart; Yanxia Li; Yanping Wang; Qingfa Wu; Baocheng Guo; Xuan Liu (Biological Conservation, 2024)

Effect of Five Seed-Coating Agents on the Germination Rate and the Evaluation of Control Effect on the Damping-Off Disease of Sugar Beet - Bizhou Zhang; Chen Aidong; Mengyuan Sun; Wenzhe Zheng; Hui Zhang; Zengjuan Fu; Shangmin Zhao; Ziqiang Zhang; Liang Wang; Yuanyuan E; Huizhong Zhang; Chen Bai; et al. (Sugar Tech, 2024)

Comparative lifespan and healthspan of nonhuman primate species common to biomedical research - Hillary F. Huber; Hannah C. Ainsworth; Ellen E. Quillen; Adam Salmon; Corinna Ross; Adinda D. Azhar; Karen Bales; Michele A. Basso; Kristine Coleman; Ricki Colman; Huda S. Darusman; William Hopkins; et al. (GeroScience, 2024)

Ameliorating the detrimental effects of chromium in wheat by silicon nanoparticles and its enriched biochar - Li Jia; Yue Song; Fangfang You; Sujun Wang; Umm e Rabiya; Xing Liu; Liping Huang; Liye Wang; Waqas ud Din Khan (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Tandem Mass Tag-based proteomic analysis of protein changes in superchilled crayfish (Procambarus clarkii) presoaked with carrageenan oligosaccharides - Lerong Qin; Han Li; Hongyan Lu; Jiwang Chen; Haibin Wang; E Liao (Food Chemistry, 2024)

Fate of soil organic carbon in estuarine mangroves: Evidences from stable isotopes and lignin biomarkers - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; Han Chen; Hua He; Mengxiao Yu; Hui Li; et al. (CATENA, 2024)

A streamlined method to generate endothelial cells from human pluripotent stem cells via transient doxycycline-inducible ETV2 activation - Allen Chilun Luo; Jiuhai Wang; Kai Wang; Yonglin Zhu; Liyan Gong; Umji Lee; Xiang Li; Daniel M. Tremmel; Ruei-Zeng Lin; Donald E. Ingber; James Gorman; Juan M. Melero-Martin (Angiogenesis, 2024)

Emerging therapeutic avenues against Cryptosporidium: A comprehensive review - Munwar Ali; Chang Xu; Jia Wang; Muhammad Fakhar-e-Alam Kulyar; Kun Li (Veterinary Parasitology, 2024)

Oxygen levels differentially attenuate the structure and diversity of microbial communities in the oceanic oxygen minimal zones - Jiaqian Li; Ningdong Xie; Xiuping Liu; Mohan Bai; Dana E. Hunt; Guangyi Wang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Positive effect of carbohydrate-metabolizing bacteria determines increasing soil organic carbon during long-term fertilization and straw returning in the black soil region of China - Yingxin LI; Yu SUN; Eiko E. KURAMAE; Shaoqing ZHANG; Enze WANG; Zongmu YAO; Fahad NASIR; Lei TIAN; Qiang GAO; Chunjie TIAN (Pedosphere, 2024)

What is the character of N deposition and its proportion to NH3 and NOX inside horticultural greenhouse? - Tiantian Miao; Huan Liu; Yu'e Li; Yunfan Wan; Tianjing Ren; Andong Cai; Bin Wang (Environmental Pollution, 2024)

Salt Stress Induces Complicated miRNA Responses of Sugar Beet (Beta vulgaris L.) - Ziqiang Zhang; Zengjuan Fu; Wenjin Chen; Liang Wang; Shangmin Zhao; E Yuanyuan; Hui Zhang; Bizhou Zhang; Mengyuan Sun; Wenzhe Zheng; Jing Dong; Zhiqi Zhang; et al. (Sugar Tech, 2024)

Protective effects of ginsenosides on ulcerative colitis: a meta-analysis and systematic review to reveal the mechanisms of action - Lingling Yuan; Wei Li; Shuangyuan Hu; Yingyi Wang; Shaofeng Wang; Huai’e Tian; Xuhui Sun; Xuli Yang; Mengyun Hu; Yi Zhang (Inflammopharmacology, 2024)

Lomb-Scargle spectral analysis of plasma’s noise for space-based laser interferometric gravitational wave antennas - Fei Xie; Wenlin Tang; Xiaoshan Ma; Xiaodong Peng; Zhen Yang; Li-E Qiang; Yuzhu Zhang; Chen Gao; Jiafeng Zhang; Fang Wang (Advances in Space Research, 2024)

P10-04 Polystyrene nanoplastics exposure during pregnancy and lactation induces testis development disorder in male offspring in mice - Y. Hu; R. Li; M. Shen; C. Wang; G. Dorj; E. Gombojav; L. Ren (Toxicology Letters, 2024)

P10-03 Polystyrene nanoplastics exposure during early life induces testis development disorder in male offspring through m6A methylation - L. Ren; Y. Hu; R. Li; M. Shen; C. Wang; G. Dorj; E. Gombojav; L. Zhang; H. Lu; X. Zhou (Toxicology Letters, 2024)

1D p-type molecular-based coordination polymer semiconductor with ultrahigh mobility - Chenhui Yu; Xinxu Zhu; Kefeng Li; Guan-E Wang; Gang Xu (Science Bulletin, 2024)

Preparation Conditions and Property Characterizations of Semi-coking Wastewater based Phenolic Resin - Shuaige Shi; Yonglin Yang; Yufei Wang; E. Zheng; Jian Li; Long Yan (Water, Air, & Soil Pollution, 2024)

Appraisal of Urban Waterlogging and Extent Damage Situation after the Devastating Flood - Shan-e-hyder Soomro; Muhammad Waseem Boota; Xiaotao Shi; Gul-e-Zehra Soomro; Yinghai Li; Muhammad Tayyab; Caihong Hu; Chengshuai Liu; Yuanyang Wang; Junaid Abdul Wahid; Mairaj Hyder Alias Aamir Soomro; Jiali Guo; et al. (Water Resources Management, 2024)

Complex ammonium oxidation demands visualized resolution - Zhihao Chen; Yonghong Wu; Jan Dolfing; Shunyao Zhuang; Baozhan Wang; Dan Li; Shan Huang; Bruce E. Rittmann (Science Bulletin, 2024)

A crustal radially anisotropic shear-wave velocity model of Northwestern Australia - Tingzi Li; Liang Zhao; Rijin Zhao; Ruth E. Murdie; Klaus Gessner; Xiaobing Xu; Kun Wang; Bo Wan; Sergi Ventosa; Huaiyu Yuan (Precambrian Research, 2024)

Fault control on sedimentation in the southern gentle slope of the Dongying Sag, Bohai Bay Basin - Hong Chen; Shaohua Xu; Chang'e Cai; Wenliang Shang; Jinxin Mao; Zhengjian Xu; Xiaogang Li; Jianping Liu; Nanxin Yin; Kaitong Luo; Chao Lei; Runchao Wang; et al. (Marine and Petroleum Geology, 2024)

Magmatic sulfide oxidation drives crustal PGE mobilization: Implications for hydrothermal PGE mineralization - Zhenggang Li; James E. Mungall; Ariadni A. Georgatou; Hao Wang; Yanhui Dong; Guangyu Shi; Ling Chen; Fengyou Chu; Xiaohu Li (Geochimica et Cosmochimica Acta, 2024)

Early arrival of the Réunion plume at the base of the Himalaya? - Yaying Wang; Lingsen Zeng; Li-E Gao; Linghao Zhao; Lilong Yan (Earth and Planetary Science Letters, 2024)

Self-assembly of cascade nanoenzyme glucose oxidase encapsulated in copper benzenedicarboxylate for wearable sweat-glucose colorimetric sensors with smartphone readout - Binghua Fan; Yongjun Wu; Hongchao Guo; Fei Yu; Li-e Liu; Songcheng Yu; Jia Wang; Yilin Wang (Analytica Chimica Acta, 2024)

Characterization of metabolites of sagittatoside B in rats using UPLC-QTOF-MS spectrometry - E. Sun; Xuan Li; Fengjuan Xu; Mingyu Li; Ke Ding; Ling Wang; Yingjie Wei; Xiaobin Jia (Natural Product Research, 2024)

Comparison of in vitro membrane permeabilities of diverse environmental chemicals with in silico predictions - Amarawan Intasiri; Siena E. Illa; Supadach Prertprawnon; Shenghong Wang; Li Li; Thomas W. Bell; Dingsheng Li (Science of The Total Environment, 2024)

Quantitative assessment, molecular docking and novel metabolic pathways reveal the interaction mechanisms between norfloxacin biodegradation and environmental implications - Yuru Yang; Xiong’e Li; Xinyi Li; Jiaxin Wang; Donghui Song (Journal of Hazardous Materials, 2024)

Effects of dietary selenized glucose on intestinal microbiota and tryptophan metabolism in rats: Assessing skatole reduction potential - Zhi Zeng; Bo Lv; Yun-e Tang; Huimin Sun; Shunfeng Li; Yuan He; Juan Wang; Zhi Wang (Environmental Research, 2024)

From cell membrane to endoplasmic reticulum: Tunable lipid membrane imaging by regulating the lipophilicity and internalization of carbon dots - Yanzhi Xing; Jiaxin Li; Han Leng; Yanfeng Zhang; Shuang E; Jianhua Wang; Xuwei Chen (Chemical Engineering Journal, 2024)

Preparation of co-doped biochar to improve electron transfer and modulate 1O2 generation: Unraveling the radical-unradical mechanism - Jingyang Zhang; Shuyi Yang; Kexin Zhou; Jiaqi Zhao; Junbo Wang; Na Li; Yuanfei Wang; Yun Li; Tao E (Chemical Engineering Journal, 2024)

Carbon-Sulfur isotope and major and trace element variations across the Permian–Triassic boundary on a shallow platform setting (Xiejiacao, South China) - Zijie Zheng; Zhong-Qiang Chen; Stephen E. Grasby; Xue Wang; Dominic Papineau; Ziheng Li; Xiangdong Wang; Lei Zhang; He Zhao; Yuangeng Huang; Xueqian Feng; Lewei Su; et al. (Chemical Geology, 2024)

Promoted growth of 1 T/2 H mixed-crystalline-phase Ca(II)-doped MoS2 nanoflower (100) crystallites: A study of efficient and selective adsorption of Pb(II) - Ying Wang; Tao E; Liang Chen; Ying Cheng; Yun Li; Shuyi Yang (Journal of Environmental Chemical Engineering, 2024)

Effect of waste leather dander biochar on soil organic carbon sequestration - Tao E; Cheng Ji; Ying Cheng; Shuyi Yang; Liang Chen; Daohan Wang; Yuanfei Wang; Yun Li (Journal of Environmental Chemical Engineering, 2024)

Insight into sodium selenite-induced metabolic reprogramming in response to main seleno-amino acid enrichment in Saccharomyces cerevisiae using metabolomics - Furong Wang; Min Yan; Ting Zhang; Zhen Tian; Xinxin Niu; Zimeng Guo; Xian Wang; Xiaoben Li; Wei Song; Yan'e Luo; Yahong Yuan; Tianli Yue (Food Bioscience, 2024)

Paleoclimatic application of spectral parameters to the eolian red clay of the Jianzha Basin, northeastern margin of the Tibetan Plateau - Chaofeng Fu; Ju’e Tian; Xinwen Xu; Yougui Song; Jun Zuo; Feng Wang; Lin Chen; Pengfei Li; Xiaoke Qiang (Science China Earth Sciences, 2024)

Identification of the correlation between land subsidence and groundwater level in Cangzhou, North China Plain, based on time-series PS-InSAR and machine-learning approaches - Mouigni Baraka Nafouanti; Junxia Li; Hexue Li; Mbega Ramadhani Ngata; Danyang Sun; Yihong Huang; Chuanfu Zhou; Lu Wang; Edwin E. Nyakilla (Hydrogeology Journal, 2024)

Complex Topology of Ubiquitin Chains Mediates Lysosomal Degradation of MrgC Proteins - Jiacheng Yu; Dan Li; Mingming Xie; Jun Xie; Zhen Wang; Xiaoping Gu; Zhengliang Ma; Yu’e Sun (Cell Biochemistry and Biophysics, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

Evolution and association analysis of SSIIIa in rice landraces of Yunnan Province - Xia Li; Xiaomeng Yang; Li’e Yang; Hafiz Ghulam Muhu-Din Ahmed; Chunlian Yao; Jiazhen Yang; Luxiang Wang; Tao Yang; Xiaoying Pu; Yawen Zeng (Biologia, 2024)

Assessment of the stabilization effect of ferrous sulfate for arsenic-contaminated soils based on chemical extraction methods and in vitro methods: Methodological differences and linkages - Ziqi Geng; Pengfei Wang; Naiyi Yin; Xiaolin Cai; Yaqi Fu; Chuanfang Fan; Xuhui Chang; Yunpeng Li; Jingnan Ma; Yanshan Cui; Peter E. Holm (Science of The Total Environment, 2024)

Mid-Holocene hydroclimatic change and hurricane activity in Central America recorded by an Isla de Mona Stalagmite - Huiru Tang; Liangcheng Tan; Yongli Gao; Jingjie Zang; Le Ma; Yanzhen Li; R. Lawrence Edwards; Hai Cheng; Ashish Sinha; Xiqian Wang; Xing Cheng; Ángel A. Garcia; et al. (Marine Geology, 2024)

Urbanization enhances channel and surface runoff: A quantitative analysis using both physical and empirical models over the Yangtze River basin - Shuzhe Huang; Yuan Gan; Nengcheng Chen; Chao Wang; Xiang Zhang; Chuxuan Li; Daniel E. Horton (Journal of Hydrology, 2024)

How effective is twitter (X) social media data for urban flood management? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Gul-e-Zehra Soomro; Xiaotao Shi; Jiali Guo; Yinghai Li; Muhammad Tayyab; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Chengshuai Liu; Yuanyang Wang; et al. (Journal of Hydrology, 2024)

Effects of significant emission changes on PM2.5 chemical composition and optical properties from 2019 to 2021 in a typical industrial city of eastern China - Xiangpeng Huang; Changping Li; Chao Pan; Yue'e Li; Wei Zheng; Guangwu Lin; Haiwei Li; Yunjiang Zhang; Junfeng Wang; Yali Lei; Jianhuai Ye; Xinlei Ge; et al. (Atmospheric Research, 2024)

Biological characteristics of Cordyceps militaris single mating-type strains - Xiu’E Li; Xin Wang; Fengji Liang; Zhaoxin Wang; Wenshuo Liu; Yupeng Ge; Shude Yang; Yu Liu; Yin Li; Xianhao Cheng; Weihuan Li (Archives of Microbiology, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Changes in soil microbe-mediated carbon, nitrogen and phosphorus cycling during spontaneous succession in abandoned Pb Zn mining areas - Sichen Wang; Xinqi Yuan; Ting Li; Jie Yang; Luoqi Zhao; Duanyang Yuan; Zhaolai Guo; Chang'e Liu; Changqun Duan (Science of The Total Environment, 2024)

Recycling of waste polyethylene in asphalt and its performance enhancement methods: A critical literature review - Hui Li; Yuzhao Han; E Guangxun; Yang Sun; Lei Wang; Xufei Liu; Jiaxing Ren; Zhijie Lin (Journal of Cleaner Production, 2024)

Transition-state defect structure: A new strategy for TiO2-based porous materials to enhance photodegradation of pollutants - Jingyang Zhang; Tao E; Ruifeng Zhou; Na Li; Yuanfei Wang; Yun Li; Shuyi Yang (Journal of Environmental Management, 2024)

Preparation of Mn modified waste dander biochar and its effect on soil carbon sequestration - Cheng Ji; Tao E; Ying Cheng; Shuyi Yang; Liang Chen; Daohan Wang; Yuanfei Wang; Yun Li (Environmental Research, 2024)

Effect of beta-cypermethrin on the reproductive capacity of female mice in advanced age - Qian-Feng Qiao; Li-Qing Wang; De-E. Yu; Na Li; Qiong-Jun Xu; Yong-Jiang Zhou (Environmental Toxicology and Pharmacology, 2024)

Cost-effective synthesis of MIL-101(Cr) from recyclable wastes and composite with polyaniline as an ion-to-electron transducer for potentiometric Pb2+ sensing - Basem E. Keshta; Haojie Yu; Li Wang; Md Alim Uddin; Heba G. El-Attar; Amr E. Keshta; Ali H. Gemeay; Fathy Hassan; Sherif M. Eid (Chemical Engineering Journal, 2024)

Peacock flaunting tail inspired-multiple interactions between black phosphorene and glass powder with safety shield fire of epoxy resin - Kunxin Wang; Guoming Yuan; Zhijun Liu; Hui Yang; Yang Li; Xiu-e Li; Kun Wu; Jun Shi (Chemical Engineering Journal, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

Effects of Nitrogen and Phosphorus Limitation on the Growth and Phosphorus Allocation of Alfalfa (Medicago sativa L.) - Yafei Hu; Cheng Qian; Xin Zhao; Junlin Li; Lin Wang; Dalin Liu; Xin’e Li (Journal of Soil Science and Plant Nutrition, 2024)

Identification and functional analysis of rare HECTD1 missense variants in human neural tube defects - Elias Oxman; Huili Li; Hong-Yan Wang; Irene E. Zohn (Human Genetics, 2024)
Neural tube defects (NTDs) are severe malformations of the central nervous system that arise from failure of neural tube closure. HECTD1 is an E3 ubiquitin ligase required for cranial neural tube closure in mouse models. NTDs in the Hectd1 mutant mouse model are due to the failure of cranial mesenchyme morphogenesis during neural fold elevation. Our earlier research has linked increased extracellular heat shock protein 90 (eHSP90) secretion to aberrant cranial mesenchyme morphogenesis in the Hectd1 model. Furthermore, overexpression of HECTD1 suppresses stress-induced eHSP90 secretion in cell lines. In this study, we report the identification of five rare HECTD1 missense sequence variants in NTD cases. The variants were found through targeted next-generation sequencing in a Chinese cohort of 352 NTD cases and 224 ethnically matched controls. We present data showing that HECTD1 is a highly conserved gene, extremely intolerant to loss-of-function mutations and missense changes. To evaluate the functional consequences of NTD-associated missense variants, functional assays in HEK293T cells were performed to examine protein expression and the ability of HECTD1 sequence variants to suppress eHSP90 secretion. One NTD-associated variant (A1084T) had significantly reduced expression in HEK293T cells. All five NTD-associated variants (p.M392V, p.T801I, p.I906V, p.A1084T, and p.P1835L) reduced regulation of eHSP90 secretion by HECTD1, while a putative benign variant (p.P2474L) did not. These findings are the first association of HECTD1 sequence variation with NTDs in humans.

The effect of Green green tea consumption on body mass index, lipoprotein, liver enzymes, and liver cancer: An updated systemic review incorporating a meta-analysis - Mingzhen Li; Yunjie Duan; Ying Wang; Lei Chen; Mohamed E. A. Abdelrahim; Jun Yan (Critical Reviews in Food Science and Nutrition, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Soil microbial communities' contributions to soil ecosystem multifunctionality in the natural restoration of abandoned metal mines - Ting Li; Sichen Wang; Chang'e Liu; Yadong Yu; Mingming Zong; Changqun Duan (Journal of Environmental Management, 2024)

NaH2PO4 synergizes with organic matter to stabilize chromium in tannery sludge - Ruijie Ge; Tao E; Ying Cheng; Yuanfei Wang; Jia Yu; Yun Li; Shuyi Yang (Journal of Environmental Management, 2024)

Consumption of ultra-processed foods and multiple health outcomes: An umbrella study of meta-analyses - Ziyi Wang; Cuncun Lu; Lu Cui; E Fenfen; Wenru Shang; Zhifei Wang; Guihang Song; Kehu Yang; Xiuxia Li (Food Chemistry, 2024)

Preservation and hydrocarbon generation potential of microalgal organic matter in product aggregates induced by Chlorella sp. MASCC-0008 - Jiajia Wang; Zuozhen Han; Chao Han; Yanyang Zhao; Zhaopeng Wang; Yongjie Zhang; Jie Li; Yuetong Zhang; Maurice E. Tucker (Chemical Geology, 2024)

Probiotic Potential of Bacillus amyloliquefaciens Isolated from Tibetan Yaks - Yuanyuan He; Feiran Li; Wenqian Zhang; Miao An; Aoyun Li; Yaping Wang; Yan Zhang; Muhammad Fakhar-e-Alam Kulyar; Mudassar Iqbal; Jiakui Li (Probiotics and Antimicrobial Proteins, 2024)

Prediction of solar energetic events impacting space weather conditions - Manolis K. Georgoulis; Stephanie L. Yardley; Jordan A. Guerra; Sophie A. Murray; Azim Ahmadzadeh; Anastasios Anastasiadis; Rafal Angryk; Berkay Aydin; Dipankar Banerjee; Graham Barnes; Alessandro Bemporad; Federico Benvenuto; et al. (Advances in Space Research, 2024)

Gut microbiota influence frailty syndrome in older adults: mechanisms and therapeutic strategies - Xiao-Ming Wang; Lu Fan; Chen-Chen Meng; Yun-Jiao Wang; Li-E Deng; Zhuo Yuan; Jun-Ping Zhang; Yan-Yang Li; Shi-Chao Lv (Biogerontology, 2024)

Exposure to particulate matter may affect semen quality via trace metals: Evidence from a retrospective cohort study on fertile males - Yuting Cheng; Jiaqi Zhu; Qiuqin Tang; Jing Wang; Jialin Feng; Yijie Zhou; Jinhui Li; Feng Pan; Xiumei Han; Chuncheng Lu; Xinru Wang; Marvin E. Langston; et al. (Chemosphere, 2024)

Annual greenhouse gas emissions from a rice paddy with different water-nitrogen management strategies in Central China - Jianling Li; Yu’e Li; Yunfan Wan; Bin Wang; Weiwei Cai; Xiaobo Qin; Zhihua Zhou; Xingyu Wang; Jianing Yuan; Qi Deng (Soil and Tillage Research, 2024)

Quaternary stratigraphic architecture of the Pearl River Mouth continental shelf, northern South China Sea: Unraveling stratigraphic imprints of tectonism, paleoceanography, and climate change - Haiteng Zhuo; Xin Nie; Ming Su; Wei Zhou; Yaping Lei; Yingmin Wang; Xuechao Peng; Yan Qiu; Weiyao Yan; Li'e Lin (Sedimentary Geology, 2024)

Mercury contents and isotope ratios in marine and terrestrial archives across the Cretaceous/Paleocene boundary - Sha Li; Stephen E. Grasby; Yi Xing; Edmund A. Jarzembowski; Qifei Wang; Haichun Zhang; Xiaoqiao Wan; Bo Wang (Earth-Science Reviews, 2024)

Single and mixture toxicity of cadmium and copper to swim bladder in early life stages of Japanese medaka (Oryzias latipes) - Xiaoqian Li; Yunyang Li; Melissa Chernick; David E. Hinton; Na Zheng; Chenyang Du; Wu Dong; Sujing Wang; Shengnan Hou (Environmental Geochemistry and Health, 2024)

Stress ratio sensitivity—a novel parameter for evaluating the shearing-based structural characteristic of loess - Meng Yao; Hui-e Chen; Hui Li; Qing wang; Yan Han; Qingbo Yu; Yibo Liu (Bulletin of Engineering Geology and the Environment, 2024)

The influence of environmental parameters on spatial variation in zoobenthic density and stable isotopes ( δ 13 C , δ 15 N , and δ 34 S ) within a large lake - Cecilia E. Heuvel; Yingming Zhao; Jan J. H. Ciborowski; Li Wang; Emilee Mancini; Aaron T. Fisk (Limnology and Oceanography, 2024)
The use of baselines in stable isotope studies to interpret food web structure is essential, but baseline isotope values are often assumed to be spatially homogeneous, even in large aquatic ecosystems. To test this assumption in large lakes, we quantified spatial variation in δ 13 C, δ 15 N (deposit‐feeding Oligochaeta and filter‐feeding Dreissena spp.), and δ 34 S ( Dreissena spp. only) and density in Lake Erie between 2014 and 2016. Lake Erie's three distinct basins differ in size, bathymetry, and nutrient loading, making it an excellent system for exploring spatial variation in stable isotopes of baseline organisms. Dreissena spp. densities were highest in the western and lowest in the seasonally hypoxic central basin, while Oligochaeta densities were relatively consistent throughout Lake Erie. Values of δ 13 C, δ 15 N, and δ 34 S exhibited distinct spatial trends that were not related to population densities but followed the west to east direction of water flow within the lake. For both taxa, δ 13 C was lower in the deeper, oligotrophic east basin than the shallow, mesotrophic west basin, and δ 15 N and δ 34 S increased from west to east. Spatial patterns of low δ 34 S in Dreissena spp. in the western and central basins were likely related to hypoxia, whereas patterns of δ 15 N in both taxa were probably related to the greater influence of agricultural land uses in the western basin. Spatial trends of stable isotopes in large lake zoobenthos are driven by complex interactions of environmental gradients, which could introduce bias in evaluations of trophic structures within aquatic ecosystems that use stable isotopes.

Wildfire‐induced increases in photosynthesis in boreal forest ecosystems of North America - Jinhyuk E. Kim; Jonathan A. Wang; Yue Li; Claudia I. Czimczik; James T. Randerson (Global Change Biology, 2024)
Observations of the annual cycle of atmospheric CO 2 in high northern latitudes provide evidence for an increase in terrestrial metabolism in Arctic tundra and boreal forest ecosystems. However, the mechanisms driving these changes are not yet fully understood. One proposed hypothesis is that ecological change from disturbance, such as wildfire, could increase the magnitude and change the phase of net ecosystem exchange through shifts in plant community composition. Yet, little quantitative work has evaluated this potential mechanism at a regional scale. Here we investigate how fire disturbance influences landscape‐level patterns of photosynthesis across western boreal North America. We use Alaska and Canadian large fire databases to identify the perimeters of wildfires, a Landsat‐derived land cover time series to characterize plant functional types (PFTs), and solar‐induced fluorescence (SIF) from the Orbiting Carbon Observatory‐2 (OCO‐2) as a proxy for photosynthesis. We analyze these datasets to characterize post‐fire changes in plant succession and photosynthetic activity using a space‐for‐time approach. We find that increases in herbaceous and sparse vegetation, shrub, and deciduous broadleaf forest PFTs during mid‐succession yield enhancements in SIF by 8–40% during June and July for 2‐ to 59‐year stands relative to pre‐fire controls. From the analysis of post‐fire land cover changes within individual ecoregions and modeling, we identify two mechanisms by which fires contribute to long‐term trends in SIF. First, increases in annual burning are shifting the stand age distribution, leading to increases in the abundance of shrubs and deciduous broadleaf forests that have considerably higher SIF during early‐ and mid‐summer. Second, fire appears to facilitate a long‐term shift from evergreen conifer to broadleaf deciduous forest in the Boreal Plain ecoregion. These findings suggest that increasing fire can contribute substantially to positive trends in seasonal CO 2 exchange without a close coupling to long‐term increases in carbon storage.

Moderate altitude exposure impacts host fasting blood glucose and serum metabolome by regulation of the intestinal flora - Dan Liu; Xiaoyan Gao; Xiaoran Huang; Yanqun Fan; Yu-E Wang; Yuelin Zhang; Xuanfu Chen; Jielu Wen; Haiwei He; Yimei Hong; Ying Liang; Yuxiao Zhang; et al. (Science of The Total Environment, 2023)

Metabolomics reveals that sulfotransferase 1 may regulate colchicine-induced liver injury - Ruoyue Huang; Chunyan Wang; Zhanxuan E. Wu; Qi Zhao; Jingyi Duan; Wen Huang; Yan Cheng; Beiwei Zhu; Fei Li (Chemico-Biological Interactions, 2023)

Direct identification of total and missing OH reactivities from light-duty gasoline vehicle exhaust in China based on LP-LIF measurement - Xuehui Liu; Zibing Yuan; Qing'e Sha; Shengrong Lou; Hongli Wang; Xin Li; Junyu Zheng; Bin Yuan; Min Shao (Journal of Environmental Sciences, 2023)

Exposure to three herbicide mixtures influenced maize root-associated microbial community structure, function and the network complexity - Qingyun Ma; Qingqing Li; Jie Wang; Rebecca E. Parales; Lin Li; Zhiyong Ruan (Environmental Pollution, 2023)

The effect of long-term controlled-release urea application on the relative abundances of plant growth-promoting microorganisms - Feng Gao; Zeli Li; Yongxiang Gao; E. Gaoyang; Mingyang Li; Chuanfu Li; Yunlong Cheng; Tianjiao Zhang; Shuo Wang; Liang Wu; Zhanbo Wei; Wenkui Zheng; et al. (European Journal of Agronomy, 2023)

Biomimetic scale-like polysaccharide-based highly-sensitive piezoresistive sensor with “shell-core” nanostructure - Weiyin Su; Shiyu Zong; Kun Lv; Jie Li; Yuyu E; Zeyu Chang; Xi Yao; Jian Wen; Shengguang Yuan; Mingguo Ma; Kun Wang; Jianxin Jiang (Chemical Engineering Journal, 2023)

A broadscale shift in antarctic temperature trends - Meijiao Xin; Xichen Li; Sharon E. Stammerjohn; Wenju Cai; Jiang Zhu; John Turner; Kyle R. Clem; Chentao Song; Wenzhu Wang; Yurong Hou (Climate Dynamics, 2023)

Application of magnetic-nanoparticle functionalized whole-cell biosensor array for bioavailability and ecotoxicity estimation at urban contaminated sites - Tingting Teng; Wei E. Huang; Guanghe Li; Xinzi Wang; Yizhi Song; Xiaoyi Tang; Dunzhu Dawa; Bo Jiang; Dayi Zhang (Science of The Total Environment, 2023)

Konjac glucomannan/low-acyl gellan gum edible coating containing thymol microcapsule regulates cell wall polysaccharides disassembly and delays postharvest softening of blueberries - Peng Huang; Jie Ding; Chunyan Liu; Hongying Li; Chenlin Wang; Yezi Lin; Dur E. Sameen; Md Alomgir Hossen; Mingrui Chen; Jing Yan; Yaowen Liu; Wen Qin (Postharvest Biology and Technology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

GPR39 Knockout Worsens Microcirculatory Response to Experimental Stroke in a Sex-Dependent Manner - Yifan Xu; Wenri H. Zhang; Elyse M. Allen; Lev M. Fedorov; Anthony P. Barnes; Zu Yuan Qian; Thierno Madjou Bah; Yuandong Li; Ruikang K. Wang; Robert E. Shangraw; Nabil J. Alkayed (Translational Stroke Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Composition, function and succession of bacterial communities in the tomato rhizosphere during continuous cropping - Lv Su; Huatai Li; Jing Wang; Wenting Gao; Xia Shu; Xiting Sun; Kesu Wang; Yan Duan; Yunpeng Liu; Eiko E. Kuramae; Ruifu Zhang; Biao Shen (Biology and Fertility of Soils, 2023)

Effect of dietary protein, vitamin E, and vitamin C levels on the growth and gonad development of hybrid male abalone (Haliotis fulgens ♂ × H. discus hannai ♀) by the orthogonal array design - Linyue Wang; Yanyu Yao; Zhen Zhao; Lu Li; Hanling Gan; Hesham E. Desouky; Xuexi Wang; Ziping Zhang (Aquaculture International, 2023)

Effect of environmental factors on expression of staphylococcal enterotoxin genes - Hong-na Li; Zhao-di Kang; Tao Wang; Tao Li; Yan-ge Yang; Wei-e Zhou; Fei Yuan (Environmental Science and Pollution Research, 2023)

Exploiting machine learning for controlled synthesis of carbon dots-based corrosion inhibitors - Haijie He; Shuang E; Li Ai; Xiaogang Wang; Jun Yao; Chuang He; Boyuan Cheng (Journal of Cleaner Production, 2023)

Evaluation of ground surface deformation in discontinuous permafrost regions along the China-Russia Crude Oil Pipelines in Northeast China using InSAR and ground surveys - Wenhui Wang; Xiaoying Jin; Huijun Jin; Xinyu Li; Xinbin Wang; Ruixia He; Yan Li; Xiaoying Li; Lizhong Wang; Wei Wang; Changlei Wei; Gangyi Zhou; et al. (Engineering Geology, 2023)

Polysaccharides-based ultra-thin membrane with high haze, conductivity, and recyclability - Weiyin Su; Zeyu Chang; Jie Li; Yuyu E; Wenkang Cai; Xi Yao; Meng Wang; Kun Wang; Jianxin Jiang (Chemical Engineering Journal, 2023)

Non-uniform dissolved oxygen distribution and high sludge concentration enhance simultaneous nitrification and denitrification in a novel air-lifting reactor for municipal wastewater treatment: A pilot-scale study - Yun Li; Shujie Liu; Lanlan Lu; Jinghou Wang; Guangrong Huang; Fuming Chen; Jian-e Zuo (Bioresource Technology, 2023)

Identification of general features in soil fungal communities modulated by phenolic acids - Lv Su; Huatai Li; Xiting Sun; Kesu Wang; Xia Shu; Wenting Gao; Yunpeng Liu; Eiko E. Kuramae; Biao Shen; Ruifu Zhang (Applied Soil Ecology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

Addition of cellulose degrading bacterial agents promoting keystone fungal-mediated cellulose degradation during aerobic composting: Construction the complex co-degradation system - Yingxin Li; Eiko E. Kuramae; Fahad Nasir; Enze Wang; Zhengang Zhang; Ji Li; Zongmu Yao; Lei Tian; Yu Sun; Shouyang Luo; Lingling Guo; Gaidi Ren; et al. (Bioresource Technology, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

CRISPR/Cas9-mediated knock-in of masu salmon (Oncorhyncus masou) elongase gene in the melanocortin-4 (mc4r) coding region of channel catfish (Ictalurus punctatus) genome - Michael Coogan; De Xing; Baofeng Su; Veronica Alston; Andrew Johnson; Mohd Khan; Karim Khalil; Ahmed Elaswad; Shangjia Li; Jinhai Wang; Cuiyu Lu; Wenwen Wang; et al. (Transgenic Research, 2023)

Metal mixture exposure and the risk for immunoglobulin A nephropathy: Evidence from weighted quantile sum regression - Shaohui Liu; Li’e Zhang; Na Luo; Mingjun Wang; Chuanqiao Tang; Jiajun Jing; Hao Chen; Qiuhua Hu; Lina Tan; Xiaoli Ma; Yunfeng Zou (Environmental Science and Pollution Research, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Novel biological nitrogen removal process for the treatment of wastewater with low carbon to nitrogen ratio: A review - Kaiyao Hu; Wenxuan Li; Yaning Wang; Bo Wang; Hao Mu; Shuang Ren; Kexin Zeng; Hongjuan Zhu; Jinming Liang; Ya'e Wang; Juqiang Xiao (Journal of Water Process Engineering, 2023)

Astrochronology and sedimentary noise modeling of Pliensbachian (Early Jurassic) sea-level changes, Paris Basin, France - Rui Zhang; David B. Kemp; Nicolas Thibault; Mads E. Jelby; Mingsong Li; Chunju Huang; Yu Sui; Zhixiang Wang; Dongyang Liu; Shizhen Jia (Earth and Planetary Science Letters, 2023)

Inter-regional environmental inequality under lasting pandemic exacerbated by residential response - Chunjin Li; Jintai Lin; Lulu Chen; Qi Cui; Yu Liu; Erin E. McDuffie; Mingxi Du; Hao Kong; Jingxu Wang (Science of The Total Environment, 2023)

A rapid chemometrics model for antioxidant substance mining of Chinese dwarf cherry [Cerasus humilis (Bge.) Sok.] based on polyphenol profile and antioxidant capacity of 30 germplasms - Yushi Zhang; Qingyu Cui; Chang-e Guo; Xiaobing Zhang; Shupeng Liu; Xiaoxue Wang; Jinjiang Zhao; Zihan Zhao; Weidong Li (Food Bioscience, 2023)

Long-term application of controlled-release potassium chloride increases maize yield by affecting soil bacterial ecology, enzymatic activity and nutrient supply - Zeli Li; Lixue Qiu; Tianjiao Zhang; Gaoyang E; Lili Zhang; Lingli Wang; Liang Wu; Yanfeng Wang; Yunfeng Zhang; Jun Dong; Wenjing Li; Zhiguang Liu; et al. (Field Crops Research, 2023)

Another Year of Record Heat for the Oceans - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Fujiang Yu; et al. (Advances in Atmospheric Sciences, 2023)
Changes in ocean heat content (OHC), salinity, and stratification provide critical indicators for changes in Earth’s energy and water cycles. These cycles have been profoundly altered due to the emission of greenhouse gasses and other anthropogenic substances by human activities, driving pervasive changes in Earth’s climate system. In 2022, the world’s oceans, as given by OHC, were again the hottest in the historical record and exceeded the previous 2021 record maximum. According to IAP/CAS data, the 0–2000 m OHC in 2022 exceeded that of 2021 by 10.9 ± 8.3 ZJ (1 Zetta Joules = 10 21 Joules); and according to NCEI/NOAA data, by 9.1 ± 8.7 ZJ. Among seven regions, four basins (the North Pacific, North Atlantic, the Mediterranean Sea, and southern oceans) recorded their highest OHC since the 1950s. The salinity-contrast index, a quantification of the “salty gets saltier—fresh gets fresher” pattern, also reached its highest level on record in 2022, implying continued amplification of the global hydrological cycle. Regional OHC and salinity changes in 2022 were dominated by a strong La Niña event. Global upper-ocean stratification continued its increasing trend and was among the top seven in 2022.

Machine learning and deep learning based on the small FT-MIR dataset for fine-grained sampling site recognition of boletus tomentipes - Jian-E Dong; Jieqing Li; Honggao Liu; Yuan-Zhong Wang (Food Research International, 2023)

Re-evaluation of equilibrium relationships involving U6+/U4+ and Fe3+/Fe2+ in hydrothermal fluids and their implications for U mineralization - Teng Deng; Guoxiang Chi; Anthony E. Williams-Jones; Zenghua Li; Yumeng Wang; Deru Xu; Zhilin Wang (Chemical Geology, 2023)

Photolysis frequency of nitrophenols derived from ambient measurements - Yuwen Peng; Bin Yuan; Suxia Yang; Sihang Wang; Xiaoyun Yang; Wenjie Wang; Jin Li; Xin Song; Caihong Wu; Jipeng Qi; E. Zheng; Chenshuo Ye; et al. (Science of The Total Environment, 2023)

The Bolometric Bond Albedo of Enceladus - Liming Li; Larry Guan; Sherry Li; Cindy Luu; Kevin Heng; Patrick M. Fry; Ellen C. Creecy; Xinyue Wang; Ronald J. Albright; Thishan D. Karandana G.; Xun Jiang; Robert A. West; et al. (Icarus, 2023)

Lacustrine-evaporitic microbial dolomite from a Plio-Pleistocene succession recovered by the SG-1 borehole in the Qaidam Basin, NE Tibetan Plateau - Yanyang Zhao; Xiangyu Wei; Zuozhen Han; Chao Han; Xiao Gao; Ruirui Meng; Qiyu Wang; Maurice E. Tucker; Minghui Li; Mónica Sánchez-Román (Chemical Geology, 2023)

Kuroshio Intrusion Combined with Coastal Currents Affects Phytoplankton in the Northern South China Sea Revealed by Lipid Biomarkers - Yaoyao Wang; Rong Bi; Jiawei Gao; Hailong Zhang; Li Li; Yang Ding; Gui’e Jin; Meixun Zhao (Journal of Ocean University of China, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Study of the internal mechanism of L-glutamate for improving the survival rate of Lactiplantibacillus plantarum LIP-1 after freeze-drying - E. Jingjing; Zhang Jingya; Ma Rongze; Chen Zichao; Yao Caiqing; Wang Ruixue; Zhang Qiaoling; Yang Ying; Li Jing; Wang Junguo (Innovative Food Science & Emerging Technologies, 2023)

Trends in elemental Pb concentrations within atmospheric PM2.5 and associated risk to human health in major cities of China - Qian Cui; Liangzhong Li; Yaqiang Cao; Bo Yang; Lindou Liu; Xiaoyan Dong; Yu'e Cha; Hongjie Ruan; Song Tang; Qiong Wang (Environmental Pollution, 2023)

Bacterial anomalies associated with deep sea hydrocarbon seepage along the Scotian Slope - Carmen Li; Oyeboade Adebayo; Deidra K. Ferguson; Scott Wang; Jayne E. Rattray; Martin Fowler; Jamie Webb; Calvin Campbell; Natasha Morrison; Adam MacDonald; Casey R.J. Hubert (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

A 1000-year hydroclimate record from the Asian summer monsoon-Westerlies transition zone in the northeastern Qinghai-Tibetan Plateau - Luo Qin; Guangxin Liu; Xiangzhong Li; E. Chongyi; Jiang Li; Changrun Wu; Xin Guan; Yuan Wang (Climatic Change, 2023)

Spatio‐temporal patterns in the woodiness of flowering plants - Ao Luo; Xiaoting Xu; Yunpeng Liu; Yaoqi Li; Xiangyan Su; Yichao Li; Tong Lyu; Dimitar Dimitrov; Markku Larjavaara; Shijia Peng; Yongsheng Chen; Qinggang Wang; et al. (Global Ecology and Biogeography, 2023)
Aim Woody and herbaceous habits represent one of the most distinct contrasts among angiosperms, and the proportion of woody species in floras (i.e., “woodiness” hereafter) represents a fundamental structural element of plant diversity. Despite its core influence on ecosystem processes, spatio‐temporal patterns in woodiness remain poorly understood. Here, we aim to demonstrate the global spatio‐temporal patterns in angiosperm woodiness and their relationship with environmental factors. Location Global. Time period Cenozoic, 66 Ma to present. Major taxa studied Angiosperms. Methods Using newly compiled data on the growth forms and distributions of c . 300,000 angiosperm species and an angiosperm phylogeny, we mapped the current global geographical patterns in angiosperm woodiness, reconstructed ancestral states of growth forms through the angiosperm phylogeny and demonstrated the Cenozoic evolutionary dynamics of woodiness. We evaluated the relationships between woodiness and current climate and palaeoclimate. Results We found that c . 42.7% of angiosperms are woody. Woodiness decreased spatially from the equator towards high latitudes, temporally since the early Cenozoic. Temperature was the best predictor of the spatio‐temporal decline in woodiness and was positively correlated with woodiness. Despite the temporal decline in woodiness, macroevolutionary herbaceous‐to‐woody transitions increased through time and contributed to the evolution of woody floras in temperate drylands, whereas the opposite transitions decreased through time and contributed to herbaceous floras in tropical and subtropical drylands. Main conclusions Our study improves understanding of the spatio‐temporal dynamics of angiosperm woodiness. Our findings suggest that temperature is likely to be a determinant of spatio‐temporal variations in woodiness, highlighting the role of temperature in maintaining the growth form composition of ecosystems. Our study also calls for attention to growth form transitions (e.g., secondary woodiness) in temperate drylands that have been neglected before.

Multi-stage planning of LID-GREI urban drainage systems in response to land-use changes - Yu Zhang; Mo Wang; Dongqing Zhang; Zhongming Lu; Amin E. Bakhshipour; Ming Liu; Zhiyu Jiang; Jianjun Li; Soon Keat Tan (Science of The Total Environment, 2023)

Effects of exogenous organic/inorganic nitrogen addition on carbon pool distribution and transformation in grassland soil - Menghan Wang; Fucui Li; Lili Dong; Xiang Wang; Liebao Han; Jørgen E. Olesen (Science of The Total Environment, 2023)

Histological types of lung cancer attributable to fine particulate, smoking, and genetic susceptibility - Xiaojie Wang; Tingting Wang; Junjie Hua; Miao Cai; Zhengmin Qian; Chongjian Wang; Haitao Li; Stephen Edward McMillin; Hannah E. Aaron; Chuanbo Xie; Hualiang Lin (Science of The Total Environment, 2023)

Airborne hyperspectral imaging of cover crops through radiative transfer process-guided machine learning - Sheng Wang; Kaiyu Guan; Chenhui Zhang; Chongya Jiang; Qu Zhou; Kaiyuan Li; Ziqi Qin; Elizabeth A. Ainsworth; Jingrui He; Jun Wu; Dan Schaefer; Lowell E. Gentry; et al. (Remote Sensing of Environment, 2023)

Prehistoric sea-salt manufacture as an adaptation strategy to coastal flooding in East China - Tongtong Zheng; Shao Lei; Zhanghua Wang (王张华); Wenjing Li; Shuwen Mei; Jiehua Wang; Michael E. Meadows (Quaternary Science Reviews, 2023)

Characterization of a new chlorimuron-ethyl-degrading strain Cedecea sp. LAM2020 and biodegradation pathway revealed by multiomics analysis - Qingyun Ma; Xiaoyan Han; Jinlong Song; Jie Wang; Qingqing Li; Rebecca E. Parales; Lin Li; Zhiyong Ruan (Journal of Hazardous Materials, 2023)

Opportunities to reduce energy consumption and CO₂ emissions from ironmaking blast furnace using CO₂ electrolysis to CO for carbon recycling - Yichao Hu; Thomas E. Rufford; Jian Chen; Liangyuan Hao; Mengran Li; Yinxuan Qiu; Sahil Garg; Victor Rudolph; Geoff Wang (Journal of Cleaner Production, 2023)

Rice straw application improves yield marginally and increases carbon footprint of double cropping paddy rice (Oryza sativa L.) - Xiaobo Qin; Yanhong Lu; Yunfan Wan; Bin Wang; Jun Nie; Yu’e Li; Yulin Liao (Field Crops Research, 2023)

Short-term ambient particulate matter pollution of different sizes and respiratory hospital admission in the Beibu Gulf area of Southern China - Haopeng Li; Lizhong Liang; Shiyu Zhang; Zhengmin (Min) Qian; Miao Cai; Xiaojie Wang; Stephen Edward McMillin; Amy E. Keith; Jing Wei; Yan Geng; Hualiang Lin (Atmospheric Environment, 2023)

An Efficient Protocol for Agrobacterium-Mediated Transformation and Regeneration of Sugar Beet (Beta vulgaris L.) based on Blade–Petiole Transition Zone Explants - Ziqiang Zhang; Huizhong Zhang; Liang Wang; Bizhou Zhang; Zengjuan Fu; Shangmin Zhao; E Yuanyuan; Wenzhe Zheng; Hui Zhang; Pingan Han; Wenjin Chen; Yue Chang; et al. (Sugar Tech, 2023)

Application of the rapid leaf A–Ci response (RACiR) technique: examples from evergreen broadleaved species - Quanhong Lin; Di Tian; Changti Zhao; Bin Wang; Zhengbing Yan; Benjamin D. Stocker; Yu’e Li; Jingyun Fang (Photosynthesis Research, 2023)

Implicit satiety goals and food-related expectations predict portion size in older adults: Findings from the BAMMBE cohort - Aimee E. Pink; Li Ling Lee; Dorrain Yanwen Low; Yifan Yang; LaiGuan Zoey Fong; Alicia Yi Hui Kang; Peijia Liu; Hyejin Kim; Yulan Wang; Parasuraman Padmanabhan; Lynne Cobiac; Balázs Gulyás; et al. (Appetite, 2023)

Environmental microplastics exposure decreases antioxidant ability, perturbs gut microbial homeostasis and metabolism in chicken - Aoyun Li; Yingli Wang; Muhammad Fakhar-e-Alam Kulyar; Mudassar Iqbal; Renhao Lai; Huaisen Zhu; Kun Li (Science of The Total Environment, 2023)

In situ formed CaSO4 on waste dander biochar to inhibit the mineralization of soil organic carbon - Cheng Ji; Shuyi Yang; Ying Cheng; Lin Liu; Daohan Wang; Shujing Zhu; Tao E; Yun Li (Science of The Total Environment, 2023)

Fabrication of P-MoO2-Fe3O4 nanobelts for efficient overall water splitting - Zhijie Cui; Tiantian Feng; Xuehong Wang; Pengfei Guo; Wenpin Wang; Mei-E Yue; Zhongcheng Li (Fuel, 2023)

Toughing epoxy nanocomposites with graphene-encapsulated liquid metal framework - Da Li; E Peng; Fei Lu; Baolong Wang; Yibo Shen; Pengxiang Liu; Li Liu; Yudong Huang; Zhen Hu (Chemical Engineering Journal, 2023)

Ethane-driven chromate and nitrate bioreductions in a membrane biofilm reactor - Zifang Chi; Shijie Ju; Wenjing Wang; Huai Li; Yi-Hao Luo; Bruce E. Rittmann (Chemical Engineering Journal, 2023)

Improved Growth and High Inheritance of Melanocortin-4 Receptor (mc4r) Mutation in CRISPR/Cas-9 Gene-Edited Channel Catfish, Ictalurus punctatus - Michael Coogan; Veronica Alston; Baofeng Su; Karim Khalil; Ahmed Elaswad; Mohd Khan; Andrew Johnson; De Xing; Shangjia Li; Jinhai Wang; Rhoda M. C. Simora; Cuiyu Lu; et al. (Marine Biotechnology, 2022)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

REGγ drives Lgr5+ stem cells to potentiate radiation induced intestinal regeneration - Xiangzhan Zhu; Minglei Yang; Zaijun Lin; Solomon Kibreab Mael; Ya Li; Lili Zhang; Yaqi Kong; Yaodong Zhang; Yuping Ren; Jianhui Li; Zimeng Wang; Ying Zhang; et al. (Science China Life Sciences, 2022)

Anthropocene Geochemical and Technological Signatures of an Experimental Landfill Bioreactor in the Central Valley of California - Gry H. Barfod; Reinhard Seiser; Ramin Yazdani; Li Wang; Charles E. Lesher; Bryan M. Jenkins; Peter Thy (Anthropocene Science, 2022)
The geochemical signatures of a 12-year-old experimental bioreactor at a California landfill are used to identify elemental concentrations and ratios that characterize the landfill and relate it to the age and state of technology of the deposited waste. The bioreactor was constructed and sealed with a synthetic liner during 2001–2002 and operated and monitored as an anaerobic digester to enhance methane production. In 2013, the bioreactor was sampled and trace element concentrations of the extracted fine fractions were determined. The concentrations normalized to a regional soil composition, reveal systematic peaks for transition metals, alkali metals, heavy metals, and various metalloids and non-metals. A group of potential solder elements (Cu, Zn, Cd, In, Sn, Pb, Bi, and Sb) shows moderate to strong co-variations and is largely attributed to household electronic components and other similar products, while elements that correlated well with rare-earth and other elements are related to the diluting effect of a soil component used as cover. Batteries show modest to little effects on the overall concentrations. Circulating fluids (recycled leachate) in the controlled reactor did not completely redistribute and homogenize the elemental signatures within the time frame of the bioreactor. It is concluded that the present experimental landfill defines an Anthropocene marker identifiable by building material (plaster), PVC plastic, and household electronic components (Pb–Sn solder). These marker elements and ratios are variably diluted by soil components identified by alkali metals, rare-earths, and high field-strength elements (Hf, Zr, Nb, and Ta).

Probiotic Potential of Bacillus licheniformis and Bacillus pumilus Isolated from Tibetan Yaks, China - Zhibo Zeng; Jiabin Zhang; Yan Li; Kewei Li; Saisai Gong; Feiran Li; Pengpeng Wang; Mudassar Iqbal; Muhammad Fakhar-e-Alam Kulyar; Jiakui Li (Probiotics and Antimicrobial Proteins, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Impact of land use on surface water quality: a case study of active agriculturally disturbed basin in China - L. Zhang; X. Liu; H. Wei; C. Yang; E. Li; Z. Wang (International Journal of Environmental Science and Technology, 2022)

Vertical community patterns of Labyrinthulomycetes protists reveal their potential importance in the oceanic biological pump - Mohan Bai; Ningdong Xie; Yaodong He; Jiaqian Li; Jackie L. Collier; Dana E. Hunt; Zackary I. Johnson; Nianzhi Jiao; Guangyi Wang (Environmental Microbiology, 2022)
Summary The biological pump plays a vital role in exporting organic particles into the deep ocean for long‐term carbon sequestration. However, much remains unknown about some of its key microbial players. In this study, Labyrinthulomycetes protists (LP) were used to understand the significance of heterotrophic microeukaryotes in the transport of particulate organic matter from the surface to the dark ocean. Unlike the sharp vertical decrease of prokaryotic biomass, the LP biomass only slightly decreased with depth and eventually exceeded prokaryotic biomass in the bathypelagic layer. Sequencing identified high diversity of the LP communities with a dominance of Aplanochytrium at all depths. Notably, ASVs that were observed in the surface layer comprised ~20% of ASVs and ~60% of sequences in each of the deeper (including bathypelagic) layers, suggesting potential vertical export of the LP populations to the deep ocean. Further analyses of the vertical patterns of the 50 most abundant ASVs revealed niche partitioning of LP phylotypes in the pelagic ocean, including those that could decompose organic detritus and/or facilitate the formation of fast‐sinking particles. Overall, this study presents several lines of evidence that the LP can be an important component of the biological pump through their multiple ecotypes in the pelagic ocean.

Another Record: Ocean Warming Continues through 2021 despite La Niña Conditions - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Zhetao Tan; et al. (Advances in Atmospheric Sciences, 2022)
The increased concentration of greenhouse gases in the atmosphere from human activities traps heat within the climate system and increases ocean heat content (OHC). Here, we provide the first analysis of recent OHC changes through 2021 from two international groups. The world ocean, in 2021, was the hottest ever recorded by humans, and the 2021 annual OHC value is even higher than last year’s record value by 14 ± 11 ZJ (1 zetta J = 10 21 J) using the IAP/CAS dataset and by 16 ± 10 ZJ using NCEI/NOAA dataset. The long-term ocean warming is larger in the Atlantic and Southern Oceans than in other regions and is mainly attributed, via climate model simulations, to an increase in anthropogenic greenhouse gas concentrations. The year-to-year variation of OHC is primarily tied to the El Niño-Southern Oscillation (ENSO). In the seven maritime domains of the Indian, Tropical Atlantic, North Atlantic, Northwest Pacific, North Pacific, Southern oceans, and the Mediterranean Sea, robust warming is observed but with distinct inter-annual to decadal variability. Four out of seven domains showed record-high heat content in 2021. The anomalous global and regional ocean warming established in this study should be incorporated into climate risk assessments, adaptation, and mitigation.

Mantle Source Components and Magmatic Evolution for the Comei Large Igneous Province: Evidence from the Early Cretaceous Niangzhong Mafic Magmatism in Tethyan Himalaya - Yaying Wang; Lingsen Zeng; Kejun Hou; Li’e Gao; Qian Wang; Linghao Zhao; Jiahao Gao; Guangxu Li (Journal of Earth Science, 2022)

Handelin extends lifespan and healthspan of Caenorhabditis elegans by reducing ROS generation and improving motor function - Huijie Zhang; Jiawei Qin; Xinqiang Lan; Weirong Zeng; Jing Zhou; Tian-E Huang; Wan-Li Xiao; Qi-Quan Wang; Sujiao Sun; Weiting Su; Wenhui Nie; Shan Yang; et al. (Biogerontology, 2022)

Investigation of the risk of valproic acid–induced tremor: clinical, neuroimaging, and genetic factors - Lili Lan; Xu Zhao; Si Jian; Cun Li; Man Wang; Qing Zhou; Shanshan Huang; Suiqiang Zhu; Huicong Kang; Heidi E. Kirsch (Psychopharmacology, 2022)

Effects of environmental factors on plant functional traits across different plant life forms in a temperate forest ecosystem - Xiaoqin Cheng; Tain Ping; Zuzheng Li; Tian Wang; Hairong Han; Howard E. Epstein (New Forests, 2022)

Circular RNA screening identifies circMYLK4 as a regulator of fast/slow myofibers in porcine skeletal muscles - Haigang Cao; Jieming Liu; Tianning Du; Yihao Liu; Xiaoyu Zhang; Yuan Guo; Jie Wang; Xiaomin Zhou; Xiao Li; Gongshe Yang; Xin’e Shi (Molecular Genetics and Genomics, 2022)
The type of myofiber is related to the quality of meat. The slow oxidized myofiber helps to increase the tenderness and juiciness of muscle. Numerous studies have shown that circRNA plays a key role in skeletal muscle development. However, the role of circRNA in porcine skeletal myofiber types is unclear. In this study, we performed high-throughput RNA sequencing to study the differential expression of circRNA in the longissimus dorsi and the soleus muscle. A total of 40,757 circRNAs were identified, of which 181 were significantly different. Interestingly, some circRNAs were involved in metabolism pathways, AMPK, FoxO, and PI3K-Akt signaling pathways. Besides, we focused on a novel circRNA-circMYLK4. By injecting circMYLK4-AAV into piglets, we found that circMYLK4 significantly increased the mRNA and protein levels of the slow muscle marker genes. In summary, our study laid an essential foundation for further research of circRNA in myofiber type conversion and higher meat quality.

The Key Regulator of Necroptosis, RIP1 Kinase, Contributes to the Formation of Astrogliosis and Glial Scar in Ischemic Stroke - Yong-Ming Zhu; Liang Lin; Chao Wei; Yi Guo; Yuan Qin; Zhong-Sheng Li; Thomas A. Kent; Claire E. McCoy; Zhan-Xiang Wang; Yong Ni; Xian-Yong Zhou; Hui-Ling Zhang (Translational Stroke Research, 2021)
Necroptosis initiation relies on the receptor-interacting protein 1 kinase (RIP1K). We recently reported that genetic and pharmacological inhibition of RIP1K produces protection against ischemic stroke-induced astrocytic injury. However, the role of RIP1K in ischemic stroke-induced formation of astrogliosis and glial scar remains unknown. Here, in a transient middle cerebral artery occlusion (tMCAO) rat model and an oxygen and glucose deprivation and reoxygenation (OGD/Re)-induced astrocytic injury model, we show that RIP1K was significantly elevated in the reactive astrocytes. Knockdown of RIP1K or delayed administration of RIP1K inhibitor Nec-1 down-regulated the glial scar markers, improved ischemic stroke-induced necrotic morphology and neurologic deficits, and reduced the volume of brain atrophy. Moreover, knockdown of RIP1K attenuated astrocytic cell death and proliferation and promoted neuronal axonal generation in a neuron and astrocyte co-culture system. Both vascular endothelial growth factor D (VEGF-D) and its receptor VEGFR-3 were elevated in the reactive astrocytes; simultaneously, VEGF-D was increased in the medium of astrocytes exposed to OGD/Re. Knockdown of RIP1K down-regulated VEGF-D gene and protein levels in the reactive astrocytes. Treatment with 400 ng/ml recombinant VEGF-D induced the formation of glial scar; conversely, the inhibitor of VEGFR-3 suppressed OGD/Re-induced glial scar formation. RIP3K and MLKL may be involved in glial scar formation. Taken together, these results suggest that RIP1K participates in the formation of astrogliosis and glial scar via impairment of normal astrocyte responses and enhancing the astrocytic VEGF-D/VEGFR-3 signaling pathways. Inhibition of RIP1K promotes the brain functional recovery partially via suppressing the formation of astrogliosis and glial scar. Graphical Abstract

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A 168-year temperature recording based on tree rings and latitude differences in temperature changes in northeast China - Yangao Jiang; Yuting Cao; Junhui Zhang; Zhuo Li; Guoqiang Shi; Shijie Han; Cassius E. O. Coombs; Chuan Liu; Xiaoguang Wang; Junwei Wang; Lin Hao; Qi Xu; et al. (International Journal of Biometeorology, 2021)

Emergy-based ecological efficiency evaluation and optimization method for logistics park - Cui Wang; Cuixia Zhang; Fagang Hu; Yuan Wang; Li’e Yu; Conghu Liu (Environmental Science and Pollution Research, 2021)

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Shifting roles of the East China Sea in the phylogeography of red nanmu in East Asia - Kai Jiang; Xin Tong; Yan‐Qian Ding; Zheng‐Wei Wang; Li‐Yuan Miao; Yue‐E Xiao; Wei‐Chang Huang; Yong‐Hong Hu; Xiao‐Yong Chen (Journal of Biogeography, 2021)
Aim The effect of eustasy driven by climatic oscillations on species diversification across the East China Sea (ECS) remains unclear. In this study, Machilus thunbergii (红楠, red nanmu in Chinese) was used as a model species to determine whether the ECS acted as either a “species pump” or “species vacuum” during the Pleistocene. Locations Eastern China, and southern and central Japan. Taxon Lauraceae. Methods Ecological niche modelling was employed to predict the potential distribution of M . thunbergii during the Last Glacial Maximum (LGM) and the last interglacial period. Nuclear microsatellite and chloroplast markers were used to reveal the phylogeographic pattern and infer the population history of 33 M . thunbergii populations. Results The ecological niche models suggested that the ECS provided potentially suitable habitats for M. thunbergii during the LGM. A sharp change in cpDNA haplotypes was found along the eastern China coasts, while microsatellites revealed a clinal pattern for genetic composition from eastern China to central Japan. The divergent lineages formed an admixture on the Zhoushan Archipelago of China and Kyushu Island of Japan. The estimated divergent and admixture times were c . 68 kyr and c . 15 kyr, corresponding to the periods where there were rising sea levels after the MIS4 glaciation and falling sea levels during the LGM, respectively. Main conclusions Machilus thunbergii probably underwent alternating population isolation during interglacial periods and connection during glacial maxima across the ECS, but such periodicity of isolation and connection seems not to have promoted diversification as suggested by the species pump hypothesis. Incipient divergence has been periodically wiped out due to frequent coalescence, rendering the ECS more like a “species vacuum”, particularly for species with relatively long generation lengths.

Variations of carbon allocation and turnover time across tropical forests - Hui Yang; Philippe Ciais; Yilong Wang; Yuanyuan Huang; Jean‐Pierre Wigneron; Ana Bastos; Jérôme Chave; Jinfeng Chang; Christopher E. Doughty; Lei Fan; Daniel Goll; Emilie Joetzjer; et al. (Global Ecology and Biogeography, 2021)
Aim The carbon sink in tropical forests is a highly uncertain component of the global carbon budget. An understanding of the processes controlling this sink requires better quantification of carbon allocation, stocks and turnover times. Location Tropical forests. Time period 2010–2017. Major taxa studied Tropical forest ecosystem. Methods We develop a novel data assimilation system using satellite‐based annual above‐ground biomass derived from L‐band vegetation optical depth with 25 km × 25 km grid spacing, together with leaf area, to constrain the 25 km × 25 km carbon allocation patterns of net primary productivity (NPP) into the wood, leaf and root pools, and their turnover times. Our average data‐driven estimates of these variables are broadly consistent with independent ground‐based estimates of NPP allocation and wood turnover from forest inventory plots. Results In tropical forest, on average, the NPP allocation into wood (0.30 ± 0.04) is significantly higher than that into leaves (0.24 ± 0.07). From the wet to dry tropics, forest NPP allocation into both wood and leaves declines slightly. The turnover times of forest leaf pools exhibit little spatial variation, whereas the turnover times of wood pools in Africa (median and interquartile range: years) are slightly longer than those in South America ( years) and Southeast Asia ( years). Our datasets reveal emergent trade‐offs across climatic and vegetation gradients between growth and life span/turnover for both wood and leaves. The spatial gradients of NPP allocation to wood/leaves are associated with canopy height, adjusted by climate condition and nutrient acquisition. The spatial gradients of wood and leaf turnover times are influenced mainly by climate and leaf characteristics. Main conclusions Our data‐driven estimates of carbon allocation and turnover times provide a basis for more detailed exploration of these mechanisms in field studies. This highlights that improved model representation of carbon allocation and turnover is necessary for more accurate prediction of future carbon dynamics.

Whole genome sequencing analysis of multidrug-resistant tuberculosis in Singapore, 2006–2018 - Cynthia B. E. Chee; Leo K. Y. Lim; Rick T. H. Ong; Li Hwei Sng; Li Yang Hsu; Vernon J. M. Lee; Yee Tang Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Soil engineering by ants facilitates plant compensation for large herbivore removal of aboveground biomass - Zhiwei Zhong; Xiaofei Li; Dirk Sanders; Yiming Liu; Ling Wang; Yvette K. Ortega; Dean E. Pearson; Deli Wang (Ecology, 2021)
The interplay between top‐down and bottom‐up processes determines ecosystem productivity. Yet, the factors that mediate the balance between these opposing forces remain poorly understood. Furthering this challenge, complex and often cryptic factors like ecosystem engineering and trait‐mediated interactions may play major roles in mediating the outcomes of top‐down and bottom‐up interactions. In semiarid grasslands of northeastern China, we conducted a large‐scale, three‐year experiment to evaluate how soil engineering by ants and plasticity in plants independently and jointly influenced the top‐down effects of grazing by a ubiquitous herbivore (cattle) on aboveground standing biomass of the dominant perennial grass, Leymus chinensis . Herbivory had strong top‐down effects, reducing L. chinensis AB by 25% relative to baseline levels without cattle or ants. In contrast, soil engineering by ants facilitated weak bottom‐up effects in the absence of herbivory. However, in the presence of herbivory, soil engineering effects were strong enough to fully offset herbivore removal of aboveground biomass. This outcome was mediated by L. chinensis ’s plasticity in reallocating growth from below‐ to aboveground biomass, a result linked to additive effects of engineers and herbivores increasing soil N availability and engineering effects improving soil structure. Soil engineering increased soil N by 12%, promoting aboveground biomass. Herbivores increased soil N by 13% via defecation, but this increase failed to offset their reductions in aboveground biomass in isolation. However, when combined, engineers and herbivores increased soil N by 26% and engineers improved soil bulk density, facilitating L. chinensis to shift resource allocations from below‐ to aboveground biomass sufficiently to fully offset herbivore suppression of aboveground biomass. Our results demonstrate that soil engineering and trait‐mediated effects of plant plasticity can strongly mediate the outcome of top‐down and bottom‐up interactions. These cryptic but perhaps ubiquitous processes may help to explain the long‐debated phenomenon of plant compensatory responses to large grazers.

A Photopolymerized Semi-Interpenetrating Polymer Networks-Based Hydrogel Incorporated with Nanoparticle for Local Chemotherapy of Tumors - Yeying Wang; Qilong Li; Jing-e Zhou; Jingwen Tan; Minghao Li; Nan Xu; Feng Qu; Jian Chen; Ji Li; Jing Wang; Zhiqiang Liang; Lei Yu; et al. (Pharmaceutical Research, 2021)

The Fracture Induced Electromagnetic Radiation: Approach and Protocol for the Stress State Assessment for Mining - V. Frid; E. Y. Wang; S. N. Mulev; D. X. Li (Geotechnical and Geological Engineering, 2021)

Knowledge of Cervical Cancer, Human Papilloma Virus (HPV) and HPV Vaccination Among Women in Northeast China - Yu-e Ning; Yao Liu; Xiao-yu Xu; Xin-yu Zhang; Ning Wang; Li-qiang Zheng (Journal of Cancer Education, 2020)
This study aimed to research the understanding and knowledge of cervical cancer, human papilloma virus (HPV), and HPV vaccination, and the acceptance of HPV vaccination, among a population of women in northeastern China. A cross-sectional survey was carried out by questionnaire to investigate knowledge of cervical cancer, HPV, and HPV vaccination. The 230 female participants were native residents of northeastern China, and their ages ranged between 18 and 65 years. Questionnaires were randomly acquired by the respondents from online and paper questionnaire distribution. The questionnaire included questions on three major aspects to record people’s perceptions of cervical cancer, HPV, and vaccines. Of the sample of 230 women surveyed, 80.9% had heard of cervical cancer, but understanding was only 15.7%; 38.3% knew about HPV; 20% knew about HPV vaccine; 39.6% agreed to receive HPV vaccination, and the remainder were mainly concerned about its safety and effectiveness. Data analysis showed that age, family income, and whether there was experience of screening all influenced knowledge of cervical cancer, but this was not statistically significant. The level of education had no obvious effect on the degree of knowledge about cervical cancer; however, with an improvement in education, women’s awareness of HPV vaccine improved significantly ( p < 0.05). Women who have received cervical cancer screening had significantly greater knowledge about cervical cancer and HPV than those with no screening ( p < 0.05). Women in northeastern China have little knowledge of cervical cancer, HPV, and HPV vaccine, lack disease knowledge, and hold a skeptical attitude about HPV vaccination. Medical institutions are the main channel providing information to these women.

The influence on carbon, nitrogen recycling, and greenhouse gas emissions under different C/N ratios by black soldier fly - Wancheng Pang; Dejia Hou; Elhosseny E. Nowar; Huanchun Chen; Jibin Zhang; Guoping Zhang; Qing Li; Shucai Wang (Environmental Science and Pollution Research, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Reduced regional cerebral venous oxygen saturation is a risk factor for the cognitive impairment in hemodialysis patients: a quantitative susceptibility mapping study - Chao Chai; Huiying Wang; Zhiqiang Chu; Jinping Li; Tianyi Qian; E. Mark Haacke; Shuang Xia; Wen Shen (Brain Imaging and Behavior, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Molecular characterization of gut microbial shift in SD rats after death for 30 days - Huan Li; E. Yang; Siruo Zhang; Jing Zhang; Lu Yuan; Ruina Liu; Shakir Ullah; Qi Wang; Nosheen Mushtaq; Yi Shi; Cuihong An; Zhenyuan Wang; et al. (Archives of Microbiology, 2020)

Constitutive androstane receptor (CAR) mediates dieldrin-induced liver tumorigenesis in mouse - Zemin Wang; Qiangen Wu; Xilin Li; James E. Klaunig (Archives of Toxicology, 2020)

Causes of slowing‐down seasonal CO 2 amplitude at Mauna Loa - Kai Wang; Yilong Wang; Xuhui Wang; Yue He; Xiangyi Li; Ralph F. Keeling; Philippe Ciais; Martin Heimann; Shushi Peng; Frédéric Chevallier; Pierre Friedlingstein; Stephen Sitch; et al. (Global Change Biology, 2020)
Changing amplitude of the seasonal cycle of atmospheric CO 2 (SCA) in the northern hemisphere is an emerging carbon cycle property. Mauna Loa (MLO) station (20°N, 156°W), which has the longest continuous northern hemisphere CO 2 record, shows an increasing SCA before the 1980s ( p 2 fertilization. This challenges the view that CO 2 fertilization is the dominant cause of emergent SCA trends at northern sites south of 40°N. The contribution of agricultural intensification on the deceleration of SCA at MLO was elusive according to land–atmosphere CO 2 flux estimated by DGVMs and atmospheric inversions. Our results also show the necessity to adequately account for changing circulation patterns in understanding carbon cycle dynamics observed from atmospheric observations and in using these observations to benchmark DGVMs.

Effect of Chinese Rice Wine on the Endogenous Protease Activity, Myofibrillar Degradation, and Quality Characteristics in Topmouth Culter ( Culter alburnus ) - Fan Wang; Jia-Liang He; Tursunay Turgun; Da-E Ge; Nurgul Rahman; Jian-Zhong Zhou; Xiao-Li Liu (Journal of Aquatic Food Product Technology, 2020)

Comparison of forest above‐ground biomass from dynamic global vegetation models with spatially explicit remotely sensed observation‐based estimates - Hui Yang; Philippe Ciais; Maurizio Santoro; Yuanyuan Huang; Wei Li; Yilong Wang; Ana Bastos; Daniel Goll; Almut Arneth; Peter Anthoni; Vivek K. Arora; Pierre Friedlingstein; et al. (Global Change Biology, 2020)
Gaps in our current understanding and quantification of biomass carbon stocks, particularly in tropics, lead to large uncertainty in future projections of the terrestrial carbon balance. We use the recently published GlobBiomass data set of forest above‐ground biomass (AGB) density for the year 2010, obtained from multiple remote sensing and in situ observations at 100 m spatial resolution to evaluate AGB estimated by nine dynamic global vegetation models (DGVMs). The global total forest AGB of the nine DGVMs is 365 ± 66 Pg C, the spread corresponding to the standard deviation between models, compared to 275 Pg C with an uncertainty of ~13.5% from GlobBiomass. Model‐data discrepancy in total forest AGB can be attributed to their discrepancies in the AGB density and/or forest area. While DGVMs represent the global spatial gradients of AGB density reasonably well, they only have modest ability to reproduce the regional spatial gradients of AGB density at scales below 1000 km. The 95th percentile of AGB density (AGB 95 ) in tropics can be considered as the potential maximum of AGB density which can be reached for a given annual precipitation. GlobBiomass data show local deficits of AGB density compared to the AGB 95 , particularly in transitional and/or wet regions in tropics. We hypothesize that local human disturbances cause more AGB density deficits from GlobBiomass than from DGVMs, which rarely represent human disturbances. We then analyse empirical relationships between AGB density deficits and forest cover changes, population density, burned areas and livestock density. Regression analysis indicated that more than 40% of the spatial variance of AGB density deficits in South America and Africa can be explained; in Southeast Asia, these factors explain only ~25%. This result suggests TRENDY v6 DGVMs tend to underestimate biomass loss from diverse and widespread anthropogenic disturbances, and as a result overestimate turnover time in AGB.

Raman‐activated sorting of antibiotic‐resistant bacteria in human gut microbiota - Yi Wang; Jiabao Xu; Lingchao Kong; Bei Li; Hang Li; Wei E. Huang; Chunmiao Zheng (Environmental Microbiology, 2020)
Summary The antibiotic‐resistant bacteria (ARB) and antibiotic‐resistant genes (ARGs) in human gut microbiota have significant impact on human health. While high throughput metagenomic sequencing reveals genotypes of microbial communities, the functionality, phenotype and heterogeneity of human gut microbiota are still elusive. In this study, we applied Raman microscopy and deuterium isotope probing (Raman–DIP) to detect metabolic active ARB (MA‐ARB) in situ at the single‐cell level in human gut microbiota from two healthy adults. We analysed the relative abundances of MA‐ARB under different concentrations of amoxicillin, cephalexin, tetracycline, florfenicol and vancomycin. To establish the link between phenotypes and genotypes of the MA‐ARB, Raman‐activated cell sorting (RACS) was used to sort MA‐ARB from human gut microbiota, and mini‐metagenomic DNA of the sorted bacteria was amplified, sequenced and analysed. The sorted MA‐ARB and their associated ARGs were identified. Our results suggest a strong relation between ARB in human gut microbiota and personal medical history. This study demonstrates that the toolkit of Raman–DIP, RACS and DNA sequencing can be useful to unravel both phenotypes and genotypes of ARB in human gut microbiota at the single‐cell level.

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Medicago truncatula adjusts root proliferation, nodule formation, and partner choice in response to local N heterogeneity - Xuechun Zhang; Lucian Wang; Judith Li; Rebecca T. Batstone; Megan E. Frederickson (Plant and Soil, 2020)

Arsenic Distribution, Accumulation and Tolerance Mechanisms of Typha angustifolia in Different Phenological Growth Stages - Guiying Yang; Huan Zhong; Xue Liu; Chang’e Liu; Shiyu Li; Lei Hou; Yungen Liu; Yan Wang; Wei Ren; Changqun Duan (Bulletin of Environmental Contamination and Toxicology, 2020)

Nonlinear responses of soil nematode community composition to increasing aridity - Dan Xiong; CunZheng Wei; E. R. Jasper Wubs; G. F. Veen; Wenju Liang; Xiaobo Wang; Qi Li; Wim H. Van der Putten; Xingguo Han (Global Ecology and Biogeography, 2020)
Aim Increasing aridity under global change is predicted to have a profound impact on the structure and functioning of terrestrial ecosystems, yet we have a poor understanding of how belowground communities respond. In order to understand the longer term responses of different trophic levels in the soil food web to increasing aridity, we investigated the abundance, richness and community similarity of the soil nematode community along a 3,200 km aridity gradient. Location A transect across semi‐arid and arid grasslands in Northern China, where the aridity ranges from .43 to .97. Time period July and August 2012. Major taxa studied Soil‐borne Nematoda. Methods We used generalized additive (mixed) models to analyse the abundance, richness and community similarity patterns of soil nematodes. We used structural equation modelling (SEM) to disentangle the direct and indirect environmental drivers (aridity, soil and plant variables) of the nematode community. Results The abundance, richness and similarity of nematode communities declined nonlinearly with increasing aridity. The most pronounced decline in nematode richness and community similarity occurred in arid conditions (aridity > .80). However, the shape of the response to aridity differed among nematode feeding groups. In arid conditions, the abundance and richness of bacterial feeders were less sensitive to changes in aridity than for fungal feeders. The SEM analysis revealed that nematode community responses to aridity were not mediated via changes in plant and soil variables, but instead were affected directly by aridity. Main conclusions Our results showed that in mesic grasslands, increasing aridity primarily caused a decline in nematode abundance, whereas increasing aridity in xeric grasslands led to a loss of nematode diversity. The nonlinear responses of nematodes to aridity could also result in nonlinear shifts in ecosystem functioning, because soil nematodes operate at various trophic levels in the soil food web, thereby influencing the performance of plants, soil biodiversity and biogeochemical cycling.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Correction to: Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Effects of Modifiers on the Growth, Photosynthesis, and Antioxidant Enzymes of Cotton Under Cadmium Toxicity - MengJie An; HaiJiang Wang; Hua Fan; J. A. Ippolito; Chunmei Meng; Yulian E.; Yingbin Li; Kaiyong Wang; Changzhou Wei (Journal of Plant Growth Regulation, 2019)

Tropical cyclone damages in Mainland China over 2005–2016: losses analysis and implications - Hong Wang; Min Xu; Anselem Onyejuruwa; Yanjun Wang; Shanshan Wen; Andrew E. Gao; Yubin Li (Environment, Development and Sustainability, 2019)

Association Between Cystatin C and the Risk of Ischemic Stroke: a Systematic Review and Meta-analysis - Yan Wang; Wei Li; Jun Yang; Mijuan Zhang; Chun’e Tian; Minjiang Ma; Qian Zhang (Journal of Molecular Neuroscience, 2019)

Correction to: Internet gaming disorder: deficits in functional and structural connectivity in the ventral tegmental area-Accumbens pathway - Ruonan Wang; Min Li; Meng Zhao; Dahua Yu; Yu Hu; Corinde E. Wiers; Gene-Jack Wang; Nora D. Volkow; Kai Yuan (Brain Imaging and Behavior, 2019)

Internet gaming disorder: deficits in functional and structural connectivity in the ventral tegmental area-Accumbens pathway - Ruonan Wang; Min Li; Meng Zhao; Dahua Yu; Yu Hu; Corinde E. Wiers; Gene-Jack Wang; Nora D. Volkow; Kai Yuan (Brain Imaging and Behavior, 2019)

Anti-secretogranin III therapy of oxygen-induced retinopathy with optimal safety - Fen Tang; Michelle E. LeBlanc; Weiwen Wang; Dan Liang; Ping Chen; Tsung-Han Chou; Hong Tian; Wei Li (Angiogenesis, 2019)

Identifying loci with breeding potential across temperate and tropical adaptation via EigenGWAS and EnvGWAS - Jing Li; Guo‐Bo Chen; Awais Rasheed; Delin Li; Kai Sonder; Cristian Zavala Espinosa; Jiankang Wang; Denise E. Costich; Patrick S. Schnable; Sarah J. Hearne; Huihui Li (Molecular Ecology, 2019)
Understanding the genomic basis of adaptation in maize is important for gene discovery and the improvement of breeding germplasm, but much remains a mystery in spite of significant population genetics and archaeological research. Identifying the signals underpinning adaptation are challenging as adaptation often coincided with genetic drift, and the base genomic diversity of the species in massive. In this study, tGBS technology was used to genotype 1,143 diverse maize accessions including landraces collected from 20 countries and elite breeding lines of tropical lowland, highland, subtropical/midaltitude and temperate ecological zones. Based on 355,442 high‐quality single nucleotide polymorphisms, 13 genomic regions were detected as being under selection using the bottom‐up searching strategy, EigenGWAS. Of the 13 selection regions, 10 were first reported, two were associated with environmental parameters via EnvGWAS, and 146 genes were enriched. Combining large‐scale genomic and ecological data in this diverse maize panel, our study supports a polygenic adaptation model of maize and offers a framework to enhance our understanding of both the mechanistic basis and the evolutionary consequences of maize domestication and adaptation. The regions identified here are promising candidates for further, targeted exploration to identify beneficial alleles and haplotypes for deployment in maize breeding.

Characterizing the changing environment of cropland in the Songnen Plain, Northeast China, from 1990 to 2015 - Yuan Zhang; Shuying Zang; Li Sun; Binghe Yan; Tianpeng Yang; Wenjia Yan; Michael E. Meadows; Cuizhen Wang; Jiaguo Qi (Journal of Geographical Sciences, 2019)

Sox11-modified mesenchymal stem cells accelerate cartilage defect repair in SD rats - Liangliang Xu; E Shunmei; Sien Lin; Yonghui Hou; Weiping Lin; Wei He; Haibin Wang; Gang Li (Cell and Tissue Research, 2019)

Changes in retinal and choroidal morphology after cerebrospinal fluid pressure reduction: a Beijing iCOP study - Lu Liu; Xiaoxia Li; Hanspeter E. Killer; Kai Cao; Jing Li; Ningli Wang (Science China Life Sciences, 2019)

Monogenic, Polygenic, and MicroRNA Markers for Ischemic Stroke - Wu Chen; Bharati Sinha; Yi Li; Larry Benowitz; Qinhua Chen; Zhenghong Zhang; Nirav J. Patel; Ali M. Aziz-Sultan; Antonio E. Chiocca; Xin Wang (Molecular Neurobiology, 2019)

Vertical distribution of fluorine in farmland soil profiles around phosphorous chemical industry factories - Mei Wang; Jin-yan Yang; Wen-yan He; Jin-xin Li; Yan-yuan Zhu; Xiao-e Yang (Environmental Science and Pollution Research, 2019)

An integrated method for calculating DEM-based RUSLE LS - Meng Wang; Jantiene E. M. Baartman; Hongming Zhang; Qinke Yang; Shuqin Li; Jiangtao Yang; Cheng Cai; Meili Wang; Coen J. Ritsema; Violette Geissen (Earth Science Informatics, 2018)

Climate change favours a destructive agricultural pest in temperate regions: late spring cold matters - Shimin Gu; Peng Han; Zhengpei Ye; Lynda E. Perkins; Jing Li; Huiqing Wang; Myron P. Zalucki; Zhaozhi Lu (Journal of Pest Science, 2018)

Collapse behavior and microstructural evolution of loess soils from the Loess Plateau of China - Wan-li Xie; Ping Li; Mao-sheng Zhang; Tian-e Cheng; Yong Wang (Journal of Mountain Science, 2018)

Responses of biotic interactions of dominant and subordinate species to decadal warming and simulated rotational grazing in Tibetan alpine meadow - Xin’e Li; Xiaoxue Zhu; Shiping Wang; Shujuan Cui; Caiyun Luo; Zhenhua Zhang; Lirong Zhang; Lili Jiang; Wangwang Lü (Science China Life Sciences, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Focusing quorum sensing signalling by nano‐magnetic assembly - Yongguang Guan; Chen‐Yu Tsao; David N. Quan; Ying Li; Lei Mei; Yingying Song; Boce Zhang; Yi Liu; Gregory F. Payne; William E. Bentley; Qin Wang (Environmental Microbiology, 2018)
Summary Quorum sensing (QS) exists widely among bacteria, enabling a transition to multicellular behaviour after bacterial populations reach a particular density. The coordination of multicellularity enables biotechnological application, dissolution of biofilms, coordination of virulence, and so forth. Here, a method to elicit and subsequently disperse multicellular behaviour among QS‐negative cells is developed using magnetic nanoparticle assembly. We fabricated magnetic nanoparticles (MNPs, ∼5 nm) that electrostatically collect wild‐type (WT) Escherichia coli BL21 cells and brings them into proximity of bioengineered E. coli [CT104 (W3110 lsrFG − luxS − pCT6 + pET‐DsRed)] reporter cells that exhibit a QS response after receiving autoinducer‐2 (AI‐2). By shortening the distance between WT and reporter cells (e.g., increasing local available AI‐2 concentrations), the QS response signalling was amplified four‐fold compared to that in native conditions without assembly. This study suggests potential applications in facilitating intercellular communication and modulating multicellular behaviours based on user‐specified designs.

A Pharmacometric Analysis of Patient-Reported Outcomes in Breast Cancer Patients Through Item Response Theory - Emilie Schindler; Lena E. Friberg; Bertram L. Lum; Bei Wang; Angelica Quartino; Chunze Li; Sandhya Girish; Jin Y. Jin; Mats O. Karlsson (Pharmaceutical Research, 2018)

Overexpression of VpPR10.1 by an efficient transformation method enhances downy mildew resistance in V. vinifera - Hang Su; Yun-Tong Jiao; Fang-Fang Wang; Yue-E Liu; Wei-Li Niu; Guo-Tian Liu; Yan Xu (Plant Cell Reports, 2018)

In vitro prebiotic effects of seaweed polysaccharides - Xiaolin Chen; Yuhao Sun; Linfeng Hu; Song Liu; Huahua Yu; Rong’e Xing; Rongfeng Li; Xueqin Wang; Pengcheng Li (Journal of Oceanology and Limnology, 2018)

Transient receptor potential vanilloid-3 (TRPV3) activation plays a central role in cardiac fibrosis induced by pressure overload in rats via TGF-β1 pathway - Yan Liu; Hanping Qi; Mingyao E; Pilong Shi; Qianhui Zhang; Shuzhi Li; Ye Wang; Yonggang Cao; Yunping Chen; Lina Ba; Jingquan Gao; Wei Huang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

A histone deacetylase gene, SlHDA3, acts as a negative regulator of fruit ripening and carotenoid accumulation - Jun-E Guo; Zongli Hu; Xiaohui Yu; Anzhou Li; Fenfen Li; Yunshu Wang; Shibing Tian; Guoping Chen (Plant Cell Reports, 2018)

Semi-Mechanistic Population Pharmacokinetic Modeling of L-Histidine Disposition and Brain Uptake in Wildtype and Pht1 Null Mice - Xiao-Xing Wang; Yang-Bing Li; Meihua R. Feng; David E. Smith (Pharmaceutical Research, 2018)

Competition for electrons between pyridine and quinoline during their simultaneous biodegradation - Hua Xu; Weihua Sun; Ning Yan; Danni Li; Xueqi Wang; Tingting Yu; Yongming Zhang; Bruce E. Rittmann (Environmental Science and Pollution Research, 2017)

Pathogenic role and therapeutic potential of pleiotrophin in mouse models of ocular vascular disease - Weiwen Wang; Michelle E. LeBlanc; Xiuping Chen; Ping Chen; Yanli Ji; Megan Brewer; Hong Tian; Samantha R. Spring; Keith A. Webster; Wei Li (Angiogenesis, 2017)

Biosynthesis of staphylococcal enterotoxin A by genetic engineering technology and determination of staphylococcal enterotoxin A in water by HPLC-ESI-TOF - Hong-na Li; Fei Yuan; Yun-jing Luo; Jian-feng Wang; Chuan-bin Zhang; Wei-e Zhou; Zhi-qin Ren; Wen-jie Wu; Feng Zhang (Environmental Science and Pollution Research, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

In Situ Enzymatic Conversion of Nannochloropsis oceanica IMET1 Biomass into Fatty Acid Methyl Esters - Yao Wang; Yi-Ying Lee; Tonya M. Santaus; Charles E. Newcomb; Jin Liu; Chris D. Geddes; Chengwu Zhang; Qiang Hu; Yantao Li (BioEnergy Research, 2017)

Geographic expansion of a rust fungus on Plumeria in Pacific and Asian countries - M. Kakishima; J.‐X. Ji; P. Zhao; Q. Wang; Y. Li; E. H. C. McKenzie (New Zealand Journal of Botany, 2017)
Plumeria species, which are distributed in tropical and subtropical regions, are commonly cultivated as ornamental trees. From the late 1980s onwards, a rust disease of Plumeria spp. caused by Coleosporium plumeriae suddenly expanded to Pacific islands from its original distribution area in Central America. More recently, this disease has been reported from many countries of America, Oceania, Asia and Africa, and it causes severe damage to these trees. The history of its expansion in Pacific and Asian countries based on specimens and literature showed that the rust fungus has rapidly spread from east to west in Pacific countries and then south to north in Asian countries. It is suggested that this rapid expansion may be related to El Niño and La Niña events and typhoons, as well as anthropogenic factors such as movement of Plumeria flowers.

Nicotine withdrawal-induced inattention is absent in alpha7 nAChR knockout mice - K. K . Higa; A. Grim; M. E. Kamenski; J. van Enkhuizen; X. Zhou; K. Li; J. C. Naviaux; L. Wang; R. K. Naviaux; M. A. Geyer; A. Markou; J. W. Young (Psychopharmacology, 2017)

Antibacterial mechanism of high-mobility group nucleosomal-binding domain 2 on the Gram-negative bacteria Escherichia coli - Heng Li; Xiao-fei Shen; Xin-e Zhou; Yan-e Shi; Lu-xia Deng; Yi Ma; Xiao-ying Wang; Jing-yu Li; Ning Huang (Journal of Zhejiang University-SCIENCE B, 2017)

Functional genes and thermophilic microorganisms responsible for arsenite oxidation from the shallow sediment of an untraversed hot spring outlet - Ye Yang; Yao Mu; Xian-Chun Zeng; Weiwei Wu; Jie Yuan; Yichen Liu; E. Guoji; Feng Luo; Xiaoming Chen; Hao Li; Jianing Wang (Ecotoxicology, 2017)

An UDP-Glucosyltransferase Gene from Barley Confers Disease Resistance to Fusarium Head Blight - Li-Ping Xing; Li-Qiang He; Jin Xiao; Qi-Guang Chen; Ming-Hao Li; Yi Shang; Yan-Fei Zhu; Pei-Du Chen; Ai-Zhong Cao; Xiu-E Wang (Plant Molecular Biology Reporter, 2017)

Coral calcification under environmental change: a direct comparison of the alkalinity anomaly and buoyant weight techniques - Verena Schoepf; Xinping Hu; Michael Holcomb; Wei-Jun Cai; Qian Li; Yongchen Wang; Hui Xu; Mark E. Warner; Todd F. Melman; Kenneth D. Hoadley; D. Tye Pettay; Yohei Matsui; et al. (Coral Reefs, 2017)

Changes in flowering functional group affect responses of community phenological sequences to temperature change - F. D. Meng; L. L. Jiang; Z. H. Zhang; S. J. Cui; J. C. Duan; S. P. Wang; C. Y. Luo; Q. Wang; Y. Zhou; X. E. Li; L. R. Zhang; B. W. Li; et al. (Ecology, 2017)
Our ability to predict how temperature modifies phenology at the community scale is limited by our lack of understanding of responses by functional groups of flowering plants. These responses differ among species with different life histories. We performed a reciprocal transplant experiment along four elevation gradients (e.g., 3,200, 3,400, 3,600 and 3,800 m) to investigate the effects of warming (transferred downward) and cooling (transferred upward) on plant flowering functional groups (FFGs) and community phenological sequences (i.e., seven phenological events). Warming significantly decreased early‐spring‐flowering (ESF) plant coverage and increased mid‐summer‐flowering plant (MSF) coverage, while cooling had the opposite effect. All community phenological events were advanced by warming and delayed by cooling except for the date of complete leaf‐coloring, which showed the opposite response. Warming and cooling could cause greater advance or delay in early‐season phenological events of the community through increased coverage of MSF species, and warming could delay late‐season phenological events of the community by increased coverage of ESF species. These results suggested that coverage change of FFGs in the community induced by temperature change could mediate the responses of the community phenological events to temperature change in the future. The response of phenological events to temperature change at the species level may not be sufficient to predict phenological responses at the community‐level due to phenological compensation between species in the community.

Evaluation and Optimization of Chemical Treatments for Reducing Yellow Discoloration of Channel Catfish ( Ictalurus punctatus ) Fillets During Cold Storage - Yilin Li; Yifen Wang; Claude E. Boyd; Terrill R. Hanson; Shaoyang Liu (Journal of Aquatic Food Product Technology, 2017)

Nicotinic cholinergic system alterations and nitrous oxide exposure in a mouse model: a hypothesis for the pathobiology of autism spectrum disorder - Luis E. F. Almeida; Li Wang; Alfia Khaibullina; Zenaide M. N. Quezado (Psychopharmacology, 2017)

Social and environmental influences on tartary buckwheat (Fagopyrum tataricum Gaertn.) varietal diversity in Yunnan, China - Mary Saunders Bulan; Jiangchong Wu; Eve Emshwiller; Mark E. Berres; Joshua L. Posner; Duoyi Peng; Xinhui Wang; Junfang Li; David E. Stoltenberg; Yanping Zhang (Genetic Resources and Crop Evolution, 2017)

Temperature sensitivity thresholds to warming and cooling in phenophases of alpine plants - Fandong Meng; Yang Zhou; Shiping Wang; Jichuang Duan; Zhenhua Zhang; Haishan Niu; Lili Jiang; Shujuan Cui; Xin’e Li; Caiyun Luo; Lrirong Zhang; Qi Wang; et al. (Climatic Change, 2016)

The regional impact of Land-Use Land-cover Change (LULCC) over West Africa from an ensemble of global climate models under the auspices of the WAMME2 project - Aaron Anthony Boone; Yongkang Xue; Fernando De Sales; Ruth E. Comer; Samson Hagos; Sarith Mahanama; Kathleen Schiro; Guoqiong Song; Guiling Wang; S. Li; Carlos R. Mechoso (Climate Dynamics, 2016)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Composite modification mechanism of cationic modifier to amphoteric modified kaolin and its effects on surface characteristics - W. B. Li; Z. Liu; Z. F. Meng; S. Ren; S. E. Xu; Y. Zhang; M. Y. Wang (International Journal of Environmental Science and Technology, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Relatively stable response of fruiting stage to warming and cooling relative to other phenological events - L. L. Jiang; S. P. Wang; F. D. Meng; J. C. Duan; H. S. Niu; G. P. Xu; X. X. Zhu; Z. H. Zhang; C. Y. Luo; S. J. Cui; Y. M. Li; X. E. Li; et al. (Ecology, 2016)
The timing of the fruit‐set stage (i.e., start and end of fruit set) is crucial in a plant's life cycle, but its response to temperature change is still unclear. We investigated the timing of seven phenological events, including fruit‐set dates during 3 yr for six alpine plants transplanted to warmer (approximately +3.5°C in soils) and cooler (approximately −3.5°C in soils) locations along an altitudinal gradient in the Tibetan area. We found that fruit‐set dates remained relatively stable under both warming and cooling during the 3‐yr transplant experiment. Three earlier phenological events (emergence of first leaf, first bud set, and first flowering) and two later phenological events (first leaf coloring and complete leaf coloring) were earlier by 4.8–8.2 d/°C and later by 3.2–7.1 d/°C in response to warming. Conversely, cooling delayed the three earlier events by 3.8–6.9 d/°C and advanced the two later events by 3.2–8.1 d/°C for all plant species. The timing of the first and/or last fruit‐set dates, however, did not change significantly compared to earlier and later phenological events. Statistical analyses also showed that the dates of fruit set were not significantly correlated or had lower correlations with changes of soil temperature relative to the earlier and later phenological events. Alpine plants may thus acclimate to changes in temperature for their fruiting function by maintaining relatively stable timings of fruit set compared with other phenological events to maximize the success of seed maturation and dispersal in response to short‐term warming or cooling.

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

De novo assembly and characterization of the leaf, bud, and fruit transcriptome from the vulnerable tree Juglans mandshurica for the development of 20 new microsatellite markers using Illumina sequencing - Zhuang Hu; Tian Zhang; Xiao-Xiao Gao; Yang Wang; Qiang Zhang; Hui-Juan Zhou; Gui-Fang Zhao; Ma-Li Wang; Keith E. Woeste; Peng Zhao (Molecular Genetics and Genomics, 2016)

Study on the removal of elemental mercury from simulated flue gas by Fe2O3-CeO2/AC at low temperature - Yan Wang; Caiting Li; Lingkui Zhao; Yin’e Xie; Xunan Zhang; Guangming Zeng; Huiyu Wu; Jie Zhang (Environmental Science and Pollution Research, 2016)

UV photolysis for enhanced phenol biodegradation in the presence of 2,4,6-trichlorophenol (TCP) - Jiaxiu Song; Wenbing Wang; Rongjie Li; Jun Zhu; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Cortical thickness and surface area in neonates at high risk for schizophrenia - Gang Li; Li Wang; Feng Shi; Amanda E. Lyall; Mihye Ahn; Ziwen Peng; Hongtu Zhu; Weili Lin; John H. Gilmore; Dinggang Shen (Brain Structure and Function, 2016)

Fine mapping of qhir8 affecting in vivo haploid induction in maize - Chenxu Liu; Wei Li; Yu Zhong; Xin Dong; Haixiao Hu; Xiaolong Tian; Lele Wang; Baojian Chen; Chen Chen; Albrecht E. Melchinger; Shaojiang Chen (Theoretical and Applied Genetics, 2015)

Modulation of social deficits and repetitive behaviors in a mouse model of autism: the role of the nicotinic cholinergic system - Li Wang; Luis E. F. Almeida; Nicholas A. Spornick; Nicholas Kenyon; Sayuri Kamimura; Alfia Khaibullina; Mehdi Nouraie; Zenaide M. N. Quezado (Psychopharmacology, 2015)

A seven-gene expression panel distinguishing clonal expansions of pre-leukemic and chronic lymphocytic leukemia B cells from normal B lymphocytes - Brian A. McCarthy; Sophia Yancopoulos; Mike Tipping; Xiao-jie Yan; Xue Ping Wang; Fiona Bennett; Wentian Li; Martin Lesser; Santanu Paul; Erin Boyle; Carolina Moreno; Rosa Catera; et al. (Immunologic Research, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Effects of acute or repeated paroxetine and fluoxetine treatment on affective behavior in male and female adolescent rats - Leslie R. Amodeo; Venuz Y. Greenfield; Danielle E. Humphrey; Veronica Varela; Joseph A. Pipkin; Shannon E. Eaton; Jelesa D. Johnson; Christopher P. Plant; Zachary R. Harmony; Li Wang; Cynthia A. Crawford (Psychopharmacology, 2015)

Changes in the abundance and structure of bacterial communities under long-term fertilization treatments in a peanut monocropping system - Wuxing Liu; Qingling Wang; Baozhan Wang; Xiaobing Wang; Ashley E. Franks; Ying Teng; Zhengao Li; Yongming Luo (Plant and Soil, 2015)

Clinical characteristics of 154 patients suspected of having Ebola virus disease in the Ebola holding center of Jui Government Hospital in Sierra Leone during the 2014 Ebola outbreak - T. Yan; J. Mu; E. Qin; Y. Wang; L. Liu; D. Wu; H. Jia; Z. Li; T. Guo; X. Wang; Y. Qin; Y. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Testing the influence of previous-year temperature and food supply on development of Nemopilema nomurai blooms - Ming Sun; Jing Dong; Jennifer E. Purcell; Yulong Li; Yan Duan; Aiyong Wang; Bin Wang (Hydrobiologia, 2015)

Satellite-Based Investigation and Evaluation of the Observational Environment of Meteorological Stations in Anhui Province, China - Yu-Bin Li; Tao Shi; Yuan-Jian Yang; Bi-Wen Wu; La-Bao Wang; Chun-E Shi; Jian-Xia Guo; Cheng-Li Ji; Hua-Yang Wen (Pure and Applied Geophysics, 2015)

Near infrared radiation protects against oxygen-glucose deprivation-induced neurotoxicity by down-regulating neuronal nitric oxide synthase (nNOS) activity in vitro - Zhanyang Yu; Zhaoyu Li; Ning Liu; Yunneng Jizhang; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Near infrared radiation rescues mitochondrial dysfunction in cortical neurons after oxygen-glucose deprivation - Zhanyang Yu; Ning Liu; Jianhua Zhao; Yadan Li; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Mechanistic Aspects of the Photodynamic Inactivation of Vancomycin-Resistant Enterococci Mediated by 5-Aminolevulinic Acid and 5-Aminolevulinic Acid Methyl Ester - Chengcheng Liu; Yingli Zhou; Li Wang; Lei Han; Jin’e Lei; Hafiz Muhammad Ishaq; Jiru Xu (Current Microbiology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Racial disparity in breast cancer survival: the impact of pre-treatment hematologic variables - Chun Wang; Jesse Civan; Yinzhi Lai; Massimo Cristofanilli; Terry Hyslop; Juan P. Palazzo; Ronald E. Myers; Bingshan Li; Zhong Ye; Kejin Zhang; Jinliang Xing; Hushan Yang (Cancer Causes & Control, 2015)

Orexins (hypocretins) contribute to fear and avoidance in rats exposed to a single episode of footshocks - Xiaoyu Chen; Huiying Wang; Zhang Lin; Sa Li; Yonghui Li; Hugo T. Bergen; Maria E. Vrontakis; Gilbert J. Kirouac (Brain Structure and Function, 2014)

15 N ‐ and 2 H proteomic stable isotope probing links nitrogen flow to archaeal heterotrophic activity - Nicholas B. Justice; Zhou Li; Yingfeng Wang; Susan E. Spaudling; Annika C. Mosier; Robert L. Hettich; Chongle Pan; Jillian F. Banfield (Environmental Microbiology, 2014)
Summary Understanding how individual species contribute to nutrient transformations in a microbial community is critical to prediction of overall ecosystem function. We conducted microcosm experiments in which floating acid mine drainage ( AMD ) microbial biofilms were submerged – recapitulating the final stage in a natural biofilm life cycle. Biofilms were amended with either 15 NH 4 + or deuterium oxide ( 2 H 2 O ) and proteomic stable isotope probing ( SIP ) was used to track the extent to which different members of the community used these molecules in protein synthesis across anaerobic iron‐reducing, aerobic iron‐reducing and aerobic iron‐oxidizing environments. S ulfobacillus spp. synthesized 15 N ‐enriched protein almost exclusively under iron‐reducing conditions whereas the L eptospirillum spp. synthesized 15 N ‐enriched protein in all conditions. There were relatively few 15 N ‐enriched archaeal proteins, and all showed low atom% enrichment, consistent with A rchaea synthesizing protein using the predominantly 14 N biomass derived from recycled biomolecules. In parallel experiments using 2 H 2 O , extensive archaeal protein synthesis was detected in all conditions. In contrast, the bacterial species showed little protein synthesis using 2 H 2 O . The nearly exclusive ability of A rchaea to synthesize proteins using 2 H 2 O may be due to archaeal heterotrophy, whereby A rchaea offset deleterious effects of 2 H by accessing 1 H generated by respiration of organic compounds.

Variation in copper and zinc tolerance and accumulation in 12 willow clones: implications for phytoextraction - Wei-dong Yang; Yu-yan Wang; Feng-liang Zhao; Zhe-li Ding; Xin-cheng Zhang; Zhi-qiang Zhu; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Ecological suitability assessment and introduction experiment on Rosa damascena trigintipetala in Sichuan Province, China - Xiao-lan Wang; Chun-jiang Su; Li Peng; Hai-e Wang; Hai-ming Wang; Wei Liu; Ping Li; Yan Fang (Journal of Mountain Science, 2014)

Improved yield and Zn accumulation for rice grain by Zn fertilization and optimized water management - Yu-yan Wang; Yan-yan Wei; Lan-xue Dong; Ling-li Lu; Ying Feng; Jie Zhang; Feng-shan Pan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Eliminating host-mediated effects demonstrates Bt maize producing Cry1F has no adverse effects on the parasitoid Cotesia marginiventris - Jun-Ce Tian; Xiang-Ping Wang; Li-Ping Long; Jörg Romeis; Steven E. Naranjo; Richard L. Hellmich; Anthony M. Shelton (Transgenic Research, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Peginterferon plus Chinese herbal therapy is associated with a higher virological response than only peginterferon therapy in chronic hepatitis C - D. Cheng; E. Liu; Y. Li; R. Liu; L. Bai; Y. Chen; Y. Wang; Y. Chu; M. Wu; G. Cheng; S. Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Carbonic anhydrase: a key regulatory and detoxifying enzyme for Karst plants - Werner E. G. Müller; Li Qiang; Heinz C. Schröder; Natalie Hönig; Daoxian Yuan; Vlad A. Grebenjuk; Francesca Mussino; Marco Giovine; Xiaohong Wang (Planta, 2014)

Dissipation of available benzo[a]pyrene in aging soil co-contaminated with cadmium and pyrene - Kai Wang; Xin-xin Chen; Zhi-qiang Zhu; Hua-gang Huang; Ting-qiang Li; Xiao-e Yang (Environmental Science and Pollution Research, 2014)

CXCR4 pathway associated with family history of melanoma - Wen-Qing Li; Jiali Han; Hans R. Widlund; Mick Correll; Yaoyu E. Wang; John Quackenbush; Martin C. Mihm; Alvaro Laga Canales; Shaowei Wu; Todd Golub; Yujin Hoshida; David J. Hunter; et al. (Cancer Causes & Control, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Towards a resistance management strategy for Helicoverpa armigera in Bt-cotton in northwestern China: an assessment of potential refuge crops - Zhao-Zhi Lu; Myron P. Zalucki; Lynda E. Perkins; Deng-Yuan Wang; Li-Li Wu (Journal of Pest Science, 2013)

Clinical and epidemiological survey and analysis of the first case of human infection with avian influenza A(H7N9) virus in Hangzhou, China - L. Xie; H. Ding; Q.-J. Kao; X.-H. Yang; Y.-Y. Wen; H.-K. Lv; Z.-P. Chen; E.-F. Chen; Z. Sun; J.-C. Pan; X.-Y. Pu; J. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

QTL mapping of stalk bending strength in a recombinant inbred line maize population - Haixiao Hu; Wenxin Liu; Zhiyi Fu; Linda Homann; Frank Technow; Hongwu Wang; Chengliang Song; Shitu Li; Albrecht E. Melchinger; Shaojiang Chen (Theoretical and Applied Genetics, 2013)

Daily MODIS 500 m reflectance anisotropy direct broadcast (DB) products for monitoring vegetation phenology dynamics - Yanmin Shuai; Crystal Schaaf; Xiaoyang Zhang; Alan Strahler; David Roy; Jeffrey Morisette; Zhuosen Wang; Joanne Nightingale; Jaime Nickeson; Andrew D. Richardson; Donghui Xie; Jindi Wang; et al. (International Journal of Remote Sensing, 2013)

Effects of Edaravone on Amyloid-β Precursor Protein Processing in SY5Y-APP695 Cells - Yue-E Shen; Yan Wang; Gui-Chun Yu; Chao Liu; Zhen-Yu Zhang; Li-Ming Zhang (Neurotoxicity Research, 2013)

Simultaneous removal of cadmium and sulfamethoxazole from aqueous solution by rice straw biochar - Xuan Han; Cheng-feng Liang; Ting-qiang Li; Kai Wang; Hua-gang Huang; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Obesity-related genetic variants, human pigmentation, and risk of melanoma - Xin Li; Liming Liang; Mingfeng Zhang; Fengju Song; Hongmei Nan; Li-E Wang; Qingyi Wei; Jeffrey E. Lee; Christopher I. Amos; Abrar A. Qureshi; Jiali Han (Human Genetics, 2013)

Defence responses of pepper (Capsicum annuum L.) infected with incompatible and compatible strains of Phytophthora capsici - Jun-E Wang; Da-Wei Li; Ying-Li Zhang; Qian Zhao; Yu-Mei He; Zhen-Hui Gong (European Journal of Plant Pathology, 2013)

Evaluation of terrestrial carbon cycle models for their response to climate variability and to CO 2 trends - Shilong Piao; Stephen Sitch; Philippe Ciais; Pierre Friedlingstein; Philippe Peylin; Xuhui Wang; Anders Ahlström; Alessandro Anav; Josep G. Canadell; Nan Cong; Chris Huntingford; Martin Jung; et al. (Global Change Biology, 2013)
The purpose of this study was to evaluate 10 process‐based terrestrial biosphere models that were used for the IPCC fifth Assessment Report. The simulated gross primary productivity ( GPP ) is compared with flux‐tower‐based estimates by Jung et al . [ Journal of Geophysical Research 116 (2011) G00J07] ( JU 11). The net primary productivity ( NPP ) apparent sensitivity to climate variability and atmospheric CO 2 trends is diagnosed from each model output, using statistical functions. The temperature sensitivity is compared against ecosystem field warming experiments results. The CO 2 sensitivity of NPP is compared to the results from four Free‐Air CO 2 Enrichment ( FACE ) experiments. The simulated global net biome productivity ( NBP ) is compared with the residual land sink ( RLS ) of the global carbon budget from Friedlingstein et al . [ Nature Geoscience 3 (2010) 811] ( FR 10). We found that models produce a higher GPP (133 ± 15 Pg C yr −1 ) than JU 11 (118 ± 6 Pg C yr −1 ). In response to rising atmospheric CO 2 concentration, modeled NPP increases on average by 16% (5–20%) per 100 ppm, a slightly larger apparent sensitivity of NPP to CO 2 than that measured at the FACE experiment locations (13% per 100 ppm). Global NBP differs markedly among individual models, although the mean value of 2.0 ± 0.8 Pg C yr −1 is remarkably close to the mean value of RLS (2.1 ± 1.2 Pg C yr −1 ). The interannual variability in modeled NBP is significantly correlated with that of RLS for the period 1980–2009. Both model‐to‐model and interannual variation in model GPP is larger than that in model NBP due to the strong coupling causing a positive correlation between ecosystem respiration and GPP in the model. The average linear regression slope of global NBP vs. temperature across the 10 models is −3.0 ± 1.5 Pg C yr −1 °C −1 , within the uncertainty of what derived from RLS (−3.9 ± 1.1 Pg C yr −1 °C −1 ). However, 9 of 10 models overestimate the regression slope of NBP vs. precipitation, compared with the slope of the observed RLS vs. precipitation. With most models lacking processes that control GPP and NBP in addition to CO 2 and climate, the agreement between modeled and observation‐based GPP and NBP can be fortuitous. Carbon–nitrogen interactions (only separable in one model) significantly influence the simulated response of carbon cycle to temperature and atmospheric CO 2 concentration, suggesting that nutrients limitations should be included in the next generation of terrestrial biosphere models.

Reducing the oxidative stress mediates the cardioprotection of bicyclol against ischemia-reperfusion injury in rats - Jie Cui; Zhi Li; Ling-bo Qian; Qin Gao; Jue Wang; Meng Xue; Xiao-e Lou; Iain C. Bruce; Qiang Xia; Hui-ping Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Moderate phosphorus application enhances Zn mobility and uptake in hyperaccumulator Sedum alfredii - Huagang Huang; Kai Wang; Zhiqiang Zhu; Tingqiang Li; Zhenli He; Xiao-e Yang; D. K. Gupta (Environmental Science and Pollution Research, 2013)

Identification of a novel bluetongue virus 1-specific B-cell epitope using a monoclonal antibody against the VP2 protein - P. Wei; E. C. Sun; N. H. Liu; T. Yang; Q. Y. Xu; J. Zhao; Y. L. Qin; Y. F. Feng; J. P. Li; W. S. Wang; C. Y. Zhang; D. L. Wu (Archives of Virology, 2013)

Genetic mapping of cuticle-associated genes in barley - C. Li; X. Ma; A. Wang; E. Nevo; G. Chen (Cereal Research Communications, 2013)

Assessment of the ecological security in the three gorges reservoir area by using the ecological footprint method - Haiming Wang; Hai’e Wang; Hongyang Sun; Xiaolan Wang; Xiaoyong Liao; Zhijian Chen; Xianwei Li (Journal of Mountain Science, 2012)

Satellite monitoring of massive green macroalgae bloom (GMB): imaging ability comparison of multi-source data and drifting velocity estimation - Ting-Wei Cui; Jie Zhang; Li-E Sun; Yong-Jun Jia; Wenjing Zhao; Zong-Ling Wang; Jun-Min Meng (International Journal of Remote Sensing, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Study on Bone Density at Various Skeletal Sites for the Diagnosis of Primary Osteoporosis - E. Jiang; Zizheng Wang; Qingle Meng; Shaohua Li; Feng Wang; Guoqiang Shao; Lele Zhang (Cell Biochemistry and Biophysics, 2012)

Genome of papaya, a fast growing tropical fruit tree - Ray Ming; Qingyi Yu; Paul H. Moore; Robert E. Paull; Nancy J. Chen; Ming-Li Wang; Yun J. Zhu; Mary A. Schuler; Jiming Jiang; Andrew H. Paterson (Tree Genetics & Genomes, 2012)

Genetic analysis and fine mapping of the Ga1-S gene region conferring cross-incompatibility in maize - Hua Zhang; Xu Liu; Yu’e Zhang; Chuan Jiang; Dezhou Cui; Huaihua Liu; Detao Li; Liwen Wang; Tingting Chen; Lihua Ning; Xia Ma; Huabang Chen (Theoretical and Applied Genetics, 2012)

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.

Characterization of Prolyl Oligopeptidase Genes Differentially Expressed Between Two Cultivars of Coffea arabica L. - Ratnesh Singh; Beth Irikura; Chifumi Nagai; Henrik H. Albert; Monto Kumagai; Robert E. Paull; Paul H. Moore; Ming-Li Wang (Tropical Plant Biology, 2011)

Facial dermatosis associated with Demodex: a case-control study - Ya-e Zhao; Yan Peng; Xiang-lan Wang; Li-ping Wu; Mei Wang; Hu-ling Yan; Sheng-xiang Xiao (Journal of Zhejiang University-SCIENCE B, 2011)

Hemodynamic responses to visual stimulation in children with sickle cell anemia - Ping Zou; Kathleen J. Helton; Matthew Smeltzer; Chin-Shang Li; Heather M. Conklin; Amar Gajjar; Winfred C. Wang; Russell E. Ware; Robert J. Ogg (Brain Imaging and Behavior, 2011)

Channelized fluids in subducted continental crust: constraints from δD–δ 18 O of quartz and fluid inclusions in quartz veins from the Chinese Continental Scientific Drilling Project - Xiaoming Sun; Li Xu; Weidong Sun; Wei Zhai; Yeheng Liang; Qian Tang; Jinlong Liang; Zeming Zhang; Kun Shen; Fangyue Wang; Mingxing Ling; Robert E. Zartman (International Geology Review, 2011)

Organism–environment interactions in a changing world: a mechanistic approach - John C. Wingfield; J. Patrick Kelley; Fréderic Angelier; Olivier Chastel; Fumin Lei; Sharon E. Lynn; Brooks Miner; Jason E. Davis; Dongming Li; Gang Wang (Journal of Ornithology, 2011)

Prevalence of segregation distortion in diploid alfalfa and its implications for genetics and breeding applications - Xuehui Li; Xiaojuan Wang; Yanling Wei; E. Charles Brummer (Theoretical and Applied Genetics, 2011)

Porous EH and EH-PEG Scaffolds as Gene Delivery Vehicles to Skeletal Muscle - Erin E. Falco; Martha O. Wang; Joshua A. Thompson; Joshua M. Chetta; Diana M. Yoon; Erik Z. Li; Mangesh M. Kulkami; Sameer Shah; Abhay Pandit; J. Scott Roth; John P. Fisher (Pharmaceutical Research, 2011)

Autoxidation of Unsaturated Lipids in Food Emulsion - Yue-E Sun; Wei-Dong Wang; Hong-Wei Chen; Chao Li (Critical Reviews in Food Science and Nutrition, 2011)

Identification of two blackleg resistance genes and fine mapping of one of these two genes in a Brassica napus canola cultivar ‘Surpass 400’ - Yunming Long; Zining Wang; Zudong Sun; Dilantha W. G. Fernando; Peter B. E. McVetty; Genyi Li (Theoretical and Applied Genetics, 2011)

Development and characterization of a mouse floxed Bmp2 osteoblast cell line that retains osteoblast genotype and phenotype - Li-an Wu; Junsheng Feng; Lynn Wang; Yan-dong Mu; Andrew Baker; Kevin J. Donly; Stephen E. Harris; Mary MacDougall; Shuo Chen (Cell and Tissue Research, 2011)

Sea ice concentration over the Antarctic Ocean from satellite pulse altimetry - YuanDe Yang; E. DongChen; HaiHong Wang; DingBo Chao; CheinWay Hwang; Fei Li; SongTao Ai (Science China Earth Sciences, 2011)

Synthesis and evaluation of new 1,2,3,4-tetrahydroisoquinoline analogs as antiglioma agents - Renukadevi Patil; Shivaputra Patil; XiangDi Wang; Fei Ma; William E. Orr; Wei Li; Charles R. Yates; Eldon E. Geisert; Duane D. Miller (Medicinal Chemistry Research, 2011)

Treatment with peginterferon versus interferon in Chinese patients with chronic hepatitis C - S. Zhao; E. Liu; K. Wei; Y. Wang; Y. Li; B. Huang; Y. Chen; P. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Biomechanical Characterization of a Micro/Macroporous Polycaprolactone Tissue Integrating Vascular Graft - Yiwei Wang; Jenny Lam; Bufa Zhang; Paul E. Tomlins; Xiongwei Li; Oya Alpar; David F. Wertheim; Allan S. Jones; Allan G. A. Coombes (Cardiovascular Engineering and Technology, 2010)

Responses of Queenright and Queenless Workers of Apis Cerana to 9-keto-2(E)-decenoic Acid, a Pheromonal Constituent of the Mandibular Gland - Ken Tan; Zheng-Wei Wang; Hua Li; Ming-Xian Yang; Christian W. W. Pirk; H. Randall Hepburn; Sarah E. Radloff (Journal of Chemical Ecology, 2010)

Molecular Characterisation of the Faecal Microbiota in Patients with Type II Diabetes - Xiaokang Wu; Chaofeng Ma; Lei Han; Muhammad Nawaz; Fei Gao; Xuyan Zhang; Pengbo Yu; Chang’an Zhao; Lianchuan Li; Aiping Zhou; Juan Wang; John E. Moore; et al. (Current Microbiology, 2010)

Novel 12-bp deletion in the coding region of the bovineNPM1 gene affects growth traits - Y. Z. Huang; E. P. Zhang; H. Chen; J. Wang; Z. J. Li; Y. T. Huai; L. Ma; X. Y. Lan; G. Ren; C. Z. Lei; X. T. Fang; J. Q. Wang (Journal of Applied Genetics, 2010)

China’s regional transport dominance: Density, proximity, and accessibility - Fengjun Jin; Chengjin Wang; Xiuwei Li; Jiao’e Wang (Journal of Geographical Sciences, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Skin Solubility Determines Maximum Transepidermal Flux for Similar Size Molecules - Qian Zhang; Jeffrey E. Grice; Peng Li; Owen G. Jepps; Guang-Ji Wang; Michael S. Roberts (Pharmaceutical Research, 2009)

Analysing the forcing mechanisms for net primary productivity changes in the Heihe River Basin, north‐west China - L. Lu; X. Li; F. Veroustraete; E. Kang; J. Wang (International Journal of Remote Sensing, 2009)

Optimizing the shoot proliferation protocol of Penthorum chinense by axillary buds - Li-Qiang Wang; Jun Yang; E. Deng; Guang-Bi Wang; Zheng-Song Peng (Biotechnology Letters, 2008)

Functional analysis reveals pleiotropic effects of rice RING-H2 finger protein gene OsBIRF1 on regulation of growth and defense responses against abiotic and biotic stresses - Huizhi Liu; Huijuan Zhang; Yayun Yang; Guojun Li; Yuxia Yang; Xiao’e Wang; B. M. Vindhya S. Basnayake; Dayong Li; Fengming Song (Plant Molecular Biology, 2008)

Vegetables- and antioxidant-related nutrients, genetic susceptibility, and non-Hodgkin lymphoma risk - Linda E. Kelemen; Sophia S. Wang; Unhee Lim; Wendy Cozen; Maryjean Schenk; Patricia Hartge; Yan Li; Nathaniel Rothman; Scott Davis; Stephen J. Chanock; Mary H. Ward; James R. Cerhan (Cancer Causes & Control, 2008)

Sequence Characterization, Polymorphism, and Chromosomal Localizations of the Porcine Capz Genes - E. Yang; H. Wang; X. X. Wu; Z. L. Tang; S. L. Yang; K. Li (Biochemical Genetics, 2008)

Y chromosomes of prehistoric people along the Yangtze River - Hui Li; Ying Huang; Laura F. Mustavich; Fan Zhang; Jing-Ze Tan; Ling-E Wang; Ji Qian; Meng-He Gao; Li Jin (Human Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Origin of seed shattering in rice (Oryza sativa L.) - Zhongwei Lin; Megan E. Griffith; Xianran Li; Zuofeng Zhu; Lubing Tan; Yongcai Fu; Wenxu Zhang; Xiangkun Wang; Daoxin Xie; Chuanqing Sun (Planta, 2007)

An ultradense genetic recombination map for Brassica napus, consisting of 13551 SRAP markers - Zudong Sun; Zining Wang; Jinxing Tu; Jiefu Zhang; Fengqun Yu; Peter B. E. McVetty; Genyi Li (Theoretical and Applied Genetics, 2007)

Porcine reproductive and respiratory syndrome virus productively infects monocyte-derived dendritic cells and compromises their antigen-presenting ability - X. Wang; M. Eaton; M. Mayer; H. Li; D. He; E. Nelson; J. Christopher-Hennings (Archives of Virology, 2007)

A comparative linkage map of oilseed rape and its use for QTL analysis of seed oil and erucic acid content - D. Qiu; C. Morgan; J. Shi; Y. Long; J. Liu; R. Li; X. Zhuang; Y. Wang; X. Tan; E. Dietrich; T. Weihmann; C. Everett; et al. (Theoretical and Applied Genetics, 2006)

Distance-Based Genome Rearrangement Phylogeny - Li-San Wang; Tandy Warnow; Bernard M. E. Moret; Robert K. Jansen; Linda A. Raubeson (Journal of Molecular Evolution, 2006)

Grassland degradation in Northern Tibet based on remote sensing data - Qingzhu Gao; Yu’e Li; Yunfan Wan; Erda Lin; Wei Xiong; Wangzha Jiangcun; Baoshan Wang; Wenfu Li (Journal of Geographical Sciences, 2006)

An Auxin-Inducible F-Box Protein CEGENDUO Negatively Regulates Auxin-Mediated Lateral Root Formation in Arabidopsis - Li Dong; Lei Wang; Yu’e Zhang; Yansheng Zhang; Xingwang Deng; Yongbiao Xue (Plant Molecular Biology, 2006)

An autosomal genomic scan for loci linked to type 2 diabetes in northern Han Chinese - J. Y. Zhao; M. M. Xiong; W. Huang; H. Wang; J. Zuo; G. D. Wu; Z. Chen; B. Q. Qiang; M. L. Zhang; J. L. Chen; W. Ding; W. T. Yuan; et al. (Journal of Molecular Medicine, 2005)

Genome-wide analysis of S-Locus F-box-like genes in Arabidopsis thaliana - Lei Wang; Li Dong; Yu’e Zhang; Yansheng Zhang; Weihua Wu; Xingwang Deng; Yongbiao Xue (Plant Molecular Biology, 2004)

QTL × environment interactions in rice. I. Heading date and plant height - Z. K. Li; S. B. Yu; H. R. Lafitte; N. Huang; B. Courtois; S. Hittalmani; C. H. M. Vijayakumar; G. F. Liu; G. C. Wang; H. E. Shashidhar; J. Y. Zhuang; K. L. Zheng; et al. (Theoretical and Applied Genetics, 2003)

A constitutive gene expression system derived from the tCUP cryptic promoter elements - K. Malik; K. Wu; X.-Q. Li; T. Martin-Heller; M. Hu; E. Foster; L. Tian; C. Wang; K. Ward; M. Jordan; D. Brown; S. Gleddie; et al. (Theoretical and Applied Genetics, 2002)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

ClC-2 Activation Modulates Regulatory Volume Decrease - H. Xiong; C. Li; E. Garami; Y. Wang; M. Ramjeesingh; K. Galley; C.E. Bear (The Journal of Membrane Biology, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)